Hierarchical FeCoP nanosheets array anchored on phenolic resin derived N-doped porous carbon as a high-efficiency bifunctional electrocatalyst for alkaline water splitting - Qin Wang; Jiaxin Pei; Xiaoya Wei; Yangyang Li; Hongxin Li; Jiangyong He; Bi Chen; Jian Li; Yu Meng; Long Yan (Fuel, 2027)

Investigation on differentiation behaviors of multiple hydrocarbon components in intra-source migration within matrix-type shale oil reservoirs - Yaohua Li; Fuqiang Xu; Xingyou Xu; Caiqin Bi; Yu Shi; Rubing Han (Fuel, 2027)

Phytochemical profiling of Manglietia chevalieri and its potential in attenuating pulmonary fibrosis: Insights into bioactive constituents - Zi-Jie Long; Mao-Mao Zheng; Yu-Hang He; Bi-Xi Tang; Zhi-Xuan Wang; Xian-Neng Lu; Xi Chen; Jia Li; Yi Zang; Juan Xiong (Phytochemistry, 2027)

Indole-3-acetic acid promotes wound healing of potato tubers by activating auxin signaling and phenylpropanoid metabolism - Lirong Yu; Tongtong Cui; Pengdong Xie; Botao Bai; Ruirui Yang; Ye Han; Yi Wang; Xin Li; Yang Bi; Dov Prusky (Postharvest Biology and Technology, 2026)

Betaine alleviates scleral remodeling in experimental myopia by regulating the TLR4/TAK1/NF-κB signaling pathway - Yinqiao Zhang; Yunxiao Xie; Zhaohui Yang; Runze Gao; Shuwen Yu; Jiawen Hao; Zhongyu Ma; Yuanting Yang; Ruixue Zhang; Hongsheng Bi; Dadong Guo (Toxicology and Applied Pharmacology, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Constraints on Paleo-Pacific Plate rollback from magmatic spatiotemporal evolution, isotopic composition variations, and crustal thickness changes: Insights from Early Cretaceous adakitic granitoids in the northeastern Asian continental margin - Xinping Li; Yu Dong; Wenchun Ge; Simiao Wang; Junhui Bi; Hao Yang; Jie Tang; Hongying Zhou; Yan Jing; Guochun Zhao (Lithos, 2026)

Effects of Hericium erinaceus powder incorporation on gluten interactions, water-state distribution, starch digestibility and quality characteristics of wheat noodles - Yu-Ling Yang; Chao Yang; Long Yang; Zhang-Jie Bi; Chang-Qing Dong; Xue-Bin Yin; Ze-Xuan Gong; Zhi-Peng Liu; Ke Bian (Food Research International, 2026)

Development of three-dimensional printable peanut protein-based emulsion gels for dysphagia and oral delivery of vitamin D3: Impact of whey protein supplementation - Luhui Wang; Lina Yu; Jie Bi; Yu Song; Yuan Gao; Mingqing Wang (Food Hydrocolloids, 2026)

Seismic behavior of corrosion-damaged reinforced concrete columns retrofitted using FRP mesh–ECC composite - Chenchen Li; Hao Huo; Ao Yang; Ke Bi; Guohua Song; Kuangyu Dai; Xiaohui Yu (Engineering Structures, 2026)

Ion-imprinted poly(ionic liquid) adsorbent for selective lithium recovery from lithium battery wastewater - Yujiao Bi; Xuejie Meng; Jinpu Yang; Tingting Huang; Zhijie Shang; Zhenjiang Yu; Hongbing Song (Desalination, 2026)

Self-compensation besides porosity nanoarchitectonics in carbons derived from high-carbon peat moss as high-performance electrode materials for supercapacitors and zinc-air batteries - Yuyan Cai; Shihao Wang; Yufei Wu; Yuhua Zhang; Jiahui Yang; Xinxin Yu; Jiajie Bi; Fengjiao Yu; Yang Yang (Bioresource Technology, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

Microbial succession and functional remodeling driven by soil habitat reconfiguration during mine site restoration sequences - Jinshuai Shi; Yucong Jiang; Jiaying Li; Tao Zhang; Changfeng Li; Yuyan Zhu; Jiaying Bi; Caihong Yu (Journal of Environmental Chemical Engineering, 2026)

Effect of sugars and non-sugar sweeteners on aroma compound release, sensory quality and physical properties of flat peach puree and derived vacuum-freeze-dried products - Liya Liu; Lichang Yan; Yu Zhang; Jihong Wu; Xin Pan; Bo Cai; Shuang Bi; Ye Liu (Food Research International, 2026)

Activation of phenylpropanoid pathway by L-phenylalanine promotes suberin polyphenolic and lignin deposition in wounded potato tubers - Lirong Yu; Wei Liang; Pengdong Xie; Tingting Su; Yingbo Tang; Yi Wang; Yang Bi; Dov Prusky (Food Chemistry, 2026)

Thermally regulated interfacial alloy evolution enables stable Zn metal anodes - Yu Zhang; Yiyang Bi; Da Zhang; Lianshan Sun; Haoran Sun; Jian Li; Zhenyu Hu; Wanqiang Liu; Gang Huang (Chemical Engineering Journal, 2026)

Conversion of biomass ash into cementitious materials with dicalcium silicate for soil stabilization - Qiyong Zhang; Zefa Lu; Jun Bi; Xiaoniu Yu; Bingxiang Yuan; Linyong Cui (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Self-powered vibration online monitoring of power transformers enabled by triboelectric nanogenerator - Qun Deng; Shijie Zhai; Xin Yu; Minghao Zhang; Daiyong Yang; Jingyao Luan; Wei Jiang; Xiangzhuang Bi; Hengyu Li; Tinghai Cheng (Chemical Engineering Journal, 2026)

Disruption of gut bacterial symbiont homeostasis in Streltzoviella insularis larvae under sublethal chlorantraniliprole exposure - Zengxin Li; Yang Zhao; Bing Bi; Yu Zhang; Hao Yang; Guocai Zhang; Jie Zhang (Journal of Insect Physiology, 2026)

Characterization of GSTz2 involved in cyantraniliprole and emamectin benzoate detoxification in Drosophila suzukii - Yongqi Yan; Chongzhi Wang; Mingzhe Li; Shiwei Guo; Xuxing Li; Jingyan Yu; Xiaoqing Fang; Rui Bi (Journal of Asia-Pacific Entomology, 2026)

Seasonal shifts in dissolved organic matter composition drive the formation of nitrogenous disinfection byproducts via a carbon-nitrogen coupling mechanism in source water - Tianyu Chen; Shiyang Yu; Qiurui Zhang; Jing Qian; Yonghong Bi; Anen He; Lingxiangyu Li; Nanwen Zhu; Jitao Lv; Zhigang Li; Yawei Wang; Guibin Jiang (Environmental Research, 2026)

Facile fabrication of robust hydrophobic-oleophilic aerogel for oil/water separation and thermal management - Dongwei Bi; Shiyao Ma; Yitong Chen; Zhen Yang; Xiao Han; Yuedan Wang; Wenfu Yu; Yulong Zhang; Yueyang Hong; Jun Yan; Huimin Zhang (Environmental Research, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

From waste phosphogypsum to MOF: Facile ligand-regulated synthesis of MOF for efficient water-evaporation-induced electricity generation - Zhikun Dai; Lingling Feng; Sizhen Bi; Huiyue Wang; Guixin Hu; Xinyao Zhang; Qianyu Wei; Xingpei Yu; Xueying Wen; Ran Niu; Jiang Gong (Chemical Engineering Journal, 2026)

Evaluation of seven forms of Bacillus altitudinis F7 in alleviating intestinal damage induced by high starch diet in Micropterus salmoides - Bi-Yun Zhang; Yu-Kai Yang; Lei Zheng; Hong-Ling Yang; Guo-He Cai; Qiu-hua Yang; Yun-Zhang Sun (Animal Feed Science and Technology, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Proximal-distal coordination engineering of iron single-atom nanozyme for synergistic multi-enzymatic-photothermal control of antibiotic-resistant bacteria - Yunsen Wang; Zhichao Yu; Xiuhui Liang; Zhilan Bi; Minglang Zou; Shuo Tian; Da Huang; Zuquan Weng; Dianping Tang; Jinfeng Kong (Journal of Hazardous Materials, 2026)

Bionic nanozyme arrays for selective identifying and discriminating sulfonylurea herbicides via recognition site mimicry - Yuqing Cheng; Tian Tian; Donghui Song; Yu Ma; Zhichun Bi; Xinjian Zhang; Ling Zhang; Yongxin Li; Hui Huang (Journal of Hazardous Materials, 2026)

Strategies and advances in recycling processes of spent lithium-ion batteries for a sustainable resource - Yuhan Guo; Yiru Chen; Susmi Anna Thomas; Liang Wang; Baiqing Zhu; Jiahua Bi; Yu Li; Junqing Pan (Journal of Environmental Chemical Engineering, 2026)

Chitosan-polyethyleneimine synergistic coating enables pH-responsive adaptive immobilization of sporadically released Cd/Zn in intensive farmland - Xinyao Wang; Gaoyuan Gu; Changlong Bi; Chong Peng; Yuanfei Wang; Yu Zhang; Shuyi Yang; Tao E (Journal of Environmental Management, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

Exploring the potential of three major polyphenolic compounds from peanuts in enhancing human health and physiological function - Lina Yu; Jie Bi; Xiaoyuan Chi; Mingqing Wang (Current Opinion in Food Science, 2026)

Synergistic multi-site engineering of bound exciton relays for near-unity PLQY and stable NIR emission in lead-free perovskite inspired 0D metal halides - Aadil Ahmad Bhat; Wengang Bi; Yan Yang; Xiyuan Zhou; Tongtong Kou; Mohd Zeeshan; William W. Yu (Chemical Engineering Journal, 2026)

Pollution risk assessment and source apportionment of metals in surface sediments of Dongping Lake, China: Quantitative identification using PMF assisted by SOM - Linsong Yu; Yanling Chu; Jing Bi; Jiabin Yu; Huayong Li; Zhigao Zhang (Environmental Geochemistry and Health, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

TRIM9-Mediated Degradation of SMAD4 Promotes Pyroptosis and Disruption of the Endothelial Barrier in Aortic Dissection Disease - Hong-Qin Bi; Tan Yang; Sheng-Lin Ling; Feng-Xu Yu (Cardiovascular Toxicology, 2026)

Linkage regimes of China's ecological engineering projects with the progress of sustainable development goals - Jia Bi; Fengchen Liu; Fu Li; Deyong Yu (Applied Geography, 2026)

Integrating Matrix Decomposition into Deep Learning for Vessel Traffic Flow Prediction in IoT Industries - Chao Zhang; Bi Yu Chen; Zehao Yuan; Qinyang Chen (Journal of Marine Science and Engineering, 2026)
Accurate forecasting of vessel traffic flow (VTF) is essential for modern maritime and port management, as it improves route-planning efficiency, reduces congestion and collision risks, and optimizes port operations. This study proposes a novel deep learning framework, namely, the Bidimensional Empirical Mode Decomposition–Nocal Convolutional Neural Network–Transformer (BEMD–NocalCNN–Transformer), for high-precision VTF prediction. The proposed framework first applies the BEMD algorithm to decompose the original time-series data into high- and low-frequency components. The NocalCNN module is then employed to extract spatial features from each component, while the Transformer module captures temporal dependencies and predicts future traffic-flow trends. The final predictions are obtained by aggregating the outputs of the high- and low-frequency components. Sensitivity analyses are conducted on key parameters, including input sequence length, learning rate, number of iterations, and convolution kernel size, to optimize the model configuration. To comprehensively evaluate the proposed framework, SVM, BPNN, RNN, LSTM, GRU, Transformer, WVMA-LSTM, and NocalCNN–Transformer were implemented and evaluated using the same CFD and Wuhan datasets, data preprocessing procedures, training–testing partitions, prediction settings, and evaluation metrics. The experimental results demonstrate that the proposed model outperforms the benchmark models and achieves substantially lower prediction errors for both the Caofeidian Promontory (CFD) and Wuhan waterways. These findings demonstrate consistent prediction performance of the proposed framework and provide a robust technical foundation for intelligent maritime traffic management and port operation optimization.

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Characterization of Viable and Non-viable Microbes in PM2.5 at a Mountain Site in Southern China - Yu Zheng; Senchao Lai; Zhaokang Ruan; Yuhong Feng; Yuhan Shen; Yaoyao Fu; Xinhui Bi; Dingli Yue; Zhifeng Shi; Yingyi Zhang (Aerosol Science and Engineering, 2026)

Experimental study on the thermodynamic response characteristics of superheated liquid under explosive boiling - Jianlei Zhang; Xinao Wang; Di Yu; Qiangqiang Hao; Jingjing Yang; Jingjie Ren; Mingshu Bi (Process Safety and Environmental Protection, 2026)

Study on failure mechanism and prediction model of horizontal tanks under fragment impact with varying filling conditions - Zilong Deng; Mingshu Bi; Yubin Mu; Di Yu; Qiangqiang Hao; Jingjie Ren (Process Safety and Environmental Protection, 2026)

Early diagenetic alteration of sediment porewater in Indian Ocean basins and its controls on rare earth elements enrichment - Fangyu Shen; Li Li; Xuefa Shi; Xiaojing Wang; Mu Huang; Hongna Liu; Miao Yu; Dongjie Bi; Jihua Liu (Geochimica et Cosmochimica Acta, 2026)

Inter-particle friction effects on submarine landslide dynamics: LBM-DEM simulations of low-aspect-ratio submerged granular collapse - Shu Zhou; Yandong Bi; Xiaolin Tan; Zhen Guo; Chongqiang Zhu; Jin Sun; Yu Huang (Computers and Geotechnics, 2026)

Cessation of nitrogen addition maintains higher soil organic carbon stability in a subtropical forest acid soil - Quan Li; Tingting Cao; Shuangbo Bi; Mianhai Zheng; Qiqian Wu; Wenjuan Yu; Man Shi; Zhikang Wang; Yuchen Lin; Yakov Kuzyakov; Xinzhang Song (CATENA, 2026)

A Non-spinal Neural Circuit for Transmitting Information of Bladder Conditions - Zhenxiang Zhu; Zhuang Liu; Zan Wang; Guangfu Cui; Mei-Yu Shi; Kunzhang Lin; Yuxiang Qiu; Tengxiao Si; Peng Chen; Qing Liu; Guo-Qiang Bi; Jie Wang; et al. (Neuroscience Bulletin, 2026)

A Novel Cyclopentane Pyridine Compound Identified from Saccharothrix syringae NRRL B-16468 by PPTase-Based Activation - Yuxing Bi; Xu Han; Guihong Yu; Yueliang Yao; Song Yang; Xuhua Mo (Current Microbiology, 2026)

Invasions of alien plants pose unprecedented challenges to China’s nature reserves under climate change - Jia-Xin Wang; Rainer W. Bussmann; Fei Qin; Yun-Fen Liang; Bao-Cai Han; Hai-Yan Bi; Tian-Tian Xue; Sheng-Xiang Yu (Biodiversity and Conservation, 2026)

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

Vesicle3D: An Integrative Platform for 3D Segmentation and Analysis of Vesicles in Cryo-electron Tomograms - Zheng-Yu Lv; Zhen-Hang Lu; Shuo Liu; Pengcheng Zhou; Pak-Ming Lau; Guo-Qiang Bi; Chang-Lu Tao (Neuroscience Bulletin, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Six previously undescribed bisabolane-type sesquiterpenes from marine derived fungus Aspergillus sp. WHUF04-170 and their antimicrobial activity - Wen-Juan Ding; Hong-Ming Huang; Yu-Ning Liu; Dan-Mei Tian; Ya-Qi Yuan; Ya-Xin Xue; Kui Hong; Hong-Kai Bi; Jin-Shan Tang (Phytochemistry, 2026)

Coupled geometric and mooring non-linearities in a non-wave-riding FPV system: An experimental study - Jianjun Chen; Hua-Dong Zheng; Yu Lei; Xun Xu; Ruichao Liu; Cheng Bi; Hongbo Zhang; Bin Wu (Ocean Engineering, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Pilot-scale study of hollow fiber nanofiltration membranes for tap water treatment: Effects of organics on filtration performance - Yiran Li; Xuejun Bi; Yuan Gao; Chentongguang Yu; Wanhe Wan; Yanfen Chen; Yue Ma; Shujuan Huang; Jianyong Feng (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Exploring molecular-level rolling friction based on cyclodextrins for lubrication - Jiao Wang; Hao Cao; Wei You; Ding Xiao; Lan Sheng; Yuan Wang; Honggang Mei; Qing Bi; Xuedong Xiao; Yuping Wang; Guangfeng Li; Chenchen Wang; et al. (Carbohydrate Polymers, 2026)

Forest development and seasonal variation drive functional reorganization of soil microbiomes and enzymatic activities - Ke Shi; Jiahui Liao; Manuel Delgado-Baquerizo; Xiaoming Zou; Han Y.H. Chen; Qing-fang Bi; Yu Fang; Zhengming Yan; Tingting Ren; Honghua Ruan (CATENA, 2026)

Microbial production of xanthohumol driven by synthetic biology approaches - Yidan Hu; Yiwen Yu; Jung-Kul Lee; Vipin Chandra Kalia; Hongtao Bi; Chunjie Gong (World Journal of Microbiology and Biotechnology, 2026)

Effects of dietary chitosan oligosaccharide on juvenile grass carp: Insight from the intestinal microbiota and metabolism - Yong Dou; Liuyang Cheng; Guihai Yu; Peize Li; Hongxu Cao; Xiangdong Bi; Wenli Zhou (Journal of Fish Biology, 2026)
Nowadays, chitosan oligosaccharide (COS) served as a feed additive has been gradually applied to aquaculture. In aims to reveal the effects of COS on the growth intestinal microbiota and metabolism of Grass carp, this experiment using the feed with 3% COS supplement was conducted. The results indicated that the growth indicators (WGR and SGR) of Grass carp were promoted significantly ( p Cetobacterium , Plesiomonas and Brevinema were enriched in the COS treatment, and the intestinal microbiota profile was improved through increasing the abundance of beneficial bacteria ( Cetobacterium ). Besides, a series of lysophosphatidylcholine (LPC) (LPC 16:2, LPC 14:0, LPC 19:2, LPC 19:1, LPC O‐16:2), lysophosphatidylethanolamine (LPE) (LPE 16:2 and LPE O‐16:2) and a butanoic acid derivative named 3‐[4‐methyl‐1‐(2‐methylpropanoyl)‐3‐oxocyclohexyl]butanoic acid were up‐regulated, and two long chain fatty acyl‐CoA (LPG) (LPG 20:2 and LPG 18:0) and LPS 20:3 belonging to lipopolysaccharide (LPS) down‐regulated in the COS treatment. Therefore the result implied that the intestinal health of Grass carp would be protected via reducing the LPS induced the intestinal oxidative stress and inflammatory injury in fish. The metabolic pathways enriched in the profile between the COS treatment and control were mainly concentrated on lipid and derivative metabolism, amino acid metabolism, carbohydrate metabolism and ones associated to the signal transduction. Based on the correlation analysis, butanoic acid was identified as the metabolic marker related to Cetobacterium and Plesiomonas , while LPC O‐16:2 was determined as the biomarker associated to Brevinema. Therefore, the application of COS gives promising results and will be a green feed additive in aquaculture.

Experimental investigation on the dynamic response of approach bridge and wharf structures under vessel collision - Yan Zhu; Cuizhu Zhao; Ming Peng; Qingxin Zhao; Jingchao Bi; Yu Huang (Ocean Engineering, 2026)

Synergistic electrocatalytic-biological degradation of Ni-EDTA in a baffled three-dimensional reactor: Performance optimization and mechanism analysis - Huihui Sheng; Yan Feng; Xinqiang Jia; Xinwei Wang; Yuyu Lu; Jingran Bi; Yanzhen Yu (Journal of Cleaner Production, 2026)

Mo/Co-Doped ZIF-67/ZSM-5 catalysts for Atmospheric co-pyrolysis of tobacco stems with urea to enhance pyrrole Yield: Pathway and mechanism analysis driven by hydrodeoxygenation - Xiaoyu Song; Shanjian Liu; Jibin Li; Dongmei Bi; Yu Ni; Hui Wang (Fuel, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

Isolation of Rhizospheric Fungi from Crocus sativus L. Rhizosphere and their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xin-Zhu Yu; Zi-hao Zhu; Xue-Wen Bi; Kun-miao Feng; Ying-jie Lu; Khalid Rahman; Bo Zhu; Lu-ping Qin; Zhen-zhen Zhang; Ting Han (Current Microbiology, 2026)

Study on the effect of heating and cooling paths on the macro- and micro-properties of red sandstone based on low-field NMR - Shuang Dang; Lin Ning; Jing Bi; Yu Zhao; Yuhang Zhao; Chaolin Wang; Zhongqian Chen (Bulletin of Engineering Geology and the Environment, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Sustainable valorization of shield tunneling spoil via silane-coupled recycled mask fibers: Interfacial enhancement and engineering performance - Yu-Zhang Bi; Xin-Po Sun; Chun-Ying Wang; Tian-Xing Ma; Xian-Lei Fu; Zhe-Yuan Jiang (Sustainable Chemistry and Pharmacy, 2026)

Investigation on high temperature co-melting characteristics of municipal solid waste incineration (MSWI) fly ash and coal fly ash: Ash fusibility and flowability - Yahui He; Shuai Chen; Haoran Dai; Yuehao Li; Yu Li; Yinfeng Wang; Lei Wang; Xiaotao Bi; Yuezhao Zhu (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Future temperature-related labour loss due to premature deaths: a multi-country study - Bo Wen; Zanfina Ademi; Yao Wu; Rongbin Xu; Pei Yu; Yanming Liu; Wenhua Yu; Tingting Ye; Wenzhong Huang; Zhengyu Yang; Yiwen Zhang; Yuxi Zhang; et al. (Environmental Research, 2026)

Shear response and economic efficiency of steel reinforced ECC hollow beam without web reinforcement: Towards lightweight structure development - Qiao Liao; Zi-Ming Tang; Bi-Xiong Li; Feng Dai; Ke-Quan Yu (Engineering Structures, 2026)

Lignin-empowered self-healing biomass ionogels for multi-modal flexible sensing - Wenlian Qiu; Jia Xin Jiang; Dong Yu Zhu; Xiao Tong Chen; Bi Rao Huang; Wu Xuan Cen; Kai Yuan Li; Xueqing Qiu (Bioresource Technology, 2026)

Computational-experimental identification of bioactive component combinations from Salvia miltiorrhiza for cardiovascular protection - Yanxia Liu; Jianing Zhang; Zewen Wang; Chaoqun Liu; Shijie Bi; Zhenzhen Xu; Bin Yu; Jiaye Tian; Yue Ren; Qun Li; Xiaoqian Huo; Yanling Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Meningitis due to pandrug resistant Chryseobacterium gleum: microbiological cure and clinical response with linezolid-based combination therapy - Leilei Wang; Yingmin Bi; Yu Zhou; Fan Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Macro-mesoscopic deterioration characteristics of MICP-improved strongly weathered phyllite under wetting-drying cycles - Yuhang Zhao; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Lin Ning; Yang Li (Bulletin of Engineering Geology and the Environment, 2026)

Investigation of Microdamage and Seepage Evolution in Sandstone Under Coupled Thermomechanical Loading and Cooling Shocks via NMR - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Lin Zhang; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2026)

Characterization of capillary water absorption in microbially modified strongly weathered phyllite under the effect of thermal fatigue - Yao Zhao; Jing Bi; Yu Zhao; Chaolin Wang; Yang Li (World Journal of Microbiology and Biotechnology, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Ginkgolide B-cyclodextrin inclusion complexes: an encapsulation strategy for improved solubility and aerosol inhalation therapy in bronchial asthma - Yuying Wang; MingLi Wei; Yan Zhang; Yuxin Liu; Xiaoshuang Bi; Xingting Fan; Jingxin Gou; Haibing He; Xing Tang; Yu Zhang; Tian Yin (Drug Delivery and Translational Research, 2026)

Spatio-temporal dynamics of Ulva prolifera green tides inundation in nearshore waters of Shandong Peninsula - Ling Meng; Tao Zou; Fanzhu Qu; Yang Yu; Xiaoli Bi (Marine Pollution Bulletin, 2026)

Trophic transfer effects of heavy metals in benthic organisms: A case study from the mangrove coast of Guangxi, China - Hongrui Bi; Xun Lu; Yu Zou; Jiang Chi; Baolin Liu; Dong Sun; Juan Yang (Marine Pollution Bulletin, 2026)

The extracellular polymeric substances and plants drive soil structural reinforcement and water retention in ground fissures - Haining Yu; Yinli Bi; Kaiwei Xu; Suping Peng; Yang Zhou; Yinchu Qiao (Rhizosphere, 2026)

Moisture migration and quality evolution of Stropharia rugosoannulata during hot air and vacuum drying: An LF-NMR approach - Kuncan Yu; Shidan Zhang; Xiufang Bi; Chunlei Ni; Xi Cao; Yuanyuan Liu (Journal of Stored Products Research, 2026)

Carrier-free dual-drug nanoplatforms cooperatively remodel macrophage and VSMC fate specifications for treating abdominal aortic aneurysm - Xianru Bi; Yuxuan Xiao; Rongjie Zhang; Wei Sun; Yu Li; Chao Qi; Jiqin Lian; Lu Lu; Yingxue Hao (Chemical Engineering Journal, 2026)

Keratan sulfate revisited: UPLC–MS/MS-based quantitative profiling reveals structural heterogeneity and deficiency in ocular pathologies - Xinping Wang; Han Zhou; Xi Liang; Yue Li; Shimei Shen; Yuxin Li; Qingfeng Niu; Bi Ning Zhang; Shuying Xu; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2026)

Thawing Characteristics of Microwave on Liquid Nitrogen Freezing Anthracite and Its Implication in Stimulating Reservoirs - Zairong Yang; Chaolin Wang; Yu Zhao; Jing Bi (Rock Mechanics and Rock Engineering, 2026)

Decoding Plant Growth-Promoting Rhizobacteria Volatile Organic Compounds Mediated Growth Promotion in Malus domestica - Nan Zeng; Dandan Wang; Jiahe Pang; Xin Yu Zhao; Chunji Li; Dingcun Zhang; Junliang Ge; Die Zhao; Rutao Gai; Ziqi Cao; Xinyue Bi; Ning Zhang; et al. (Journal of Plant Growth Regulation, 2026)

LCN2 aggravates sepsis-induced ALI by inhibiting MUC1 to activate ER-stress-autophagy induced ferroptosis via lactate/MCT1/AMPK/mTOR axis - Si-Xia Chen; Xing Qi; Xiang-Tao Zheng; Zhi-Ming Bi; Yu Zhang; Yu-Ming Wang (Apoptosis, 2026)

Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Experimental study on explosive boiling of superheated liquid caused by vessel crack propagation - Di Yu; Mingshu Bi; Qiangqiang Hao; Zilong Deng; Yubin Mu; Jinghao Zhang; Jianlei Zhang; Jingjie Ren (Process Safety and Environmental Protection, 2026)

Probabilistic space-time prisms in road networks with travel time uncertainties - Hui-Ping Chen; Zhi-Chun Li; Bi Yu Chen (Journal of Transport Geography, 2026)

Drivers of biogenic secondary organic aerosols in Eastern China: Evidence from machine learning and high-resolution measurements - Kun Zhang; Meng Xiu; Xiaohui Bi; Yanan Yi; Rui Li; Biao Zhou; Ruixin Pan; Hui Chen; Jian Zhen Yu; Li Li (Journal of Hazardous Materials, 2026)

Seasonal dynamics and stability of gut antibiotic resistance genes in plateau pika (Ochotona curzoniae) and plateau zokor (Eospalax baileyi) - Yu Wang; Yuan Qian; Chenwei Shi; Jie Bi; Pengcheng Dong; Yongqiang Zou; Yayuan Yang; Yuanqing Tao; Huan Li (Journal of Hazardous Materials, 2026)

Insights into the co-combustion properties and NOx emissions of ammonia/dimethoxymethane via ReaxFF molecular dynamics and kinetic numerical simulations - Huanhuan Qin; Shujia Zhou; Tiantian Xu; Yaolei Zhao; Jie Yu; Yulei Guan; Weiyu Bi (Fuel, 2026)

Wake evolution and vacuum length in granular flows impacting obstacles: DEM simulations and analytical solutions - Yi-Han Wu; Zhi-Yuan Zhu; Lu Zheng; Dong-Po Wang; Gang Luo; Yu-Zhang Bi (Computers and Geotechnics, 2026)

Experimental Study on the Influence of Wet–Dry Cycle on the Shear Strength and Shear Fracture Morphology of Rock - Huasu Wang; Jing Bi; Yu Zhao; Chaolin Wang; Wei Wang (Rock Mechanics and Rock Engineering, 2026)

Seismic performance of beam-column joints reinforced with ECC - Long Liu; Hongbo Xiao; Songqiang Wan; Chunling Yan; Yu Wang; Chong Liu; Xiaoze Yang; Liang Cui; Chenjie Hao; Menghao Ming; Boyang Liu; Yingying Bi (Bulletin of Earthquake Engineering, 2026)

Projection-based molecular feature maps for CNN-driven nephrotoxicity prediction - Muhammad Zafar Irshad Khan; Jia-Nan Ren; Hong-Yu-Xiang Ye; Cheng Cao; Xiao-Bi Liu; Jian-Zhong Chen (Archives of Toxicology, 2026)

Cold stress reshapes gut microbiota and antibiotic resistance in ornamental fish (Cyprinus carpio) - Chenwei Shi; Yu Wang; Yuan Qian; Jie Bi; Qiaoling Yu; Jiapeng Qu; Huan Li (Antonie van Leeuwenhoek, 2026)

Directional Hydraulic Fracturing in Lushan Shale: Effects of Stress Magnitude and Pre-crack Angle on Fracture Propagation - Anfa Long; Yongfa Zhang; Yu Zhao; Shengfeng Wu; Chaolin Wang; Jing Bi; Huasen Huang; Kai Wang (Rock Mechanics and Rock Engineering, 2026)

Contaminant migration in vadose zone beneath unregulated landfills with damaged geomembranes - Yu-Zhang Bi; Xin-Po Sun; Qi Zou; Zhe-Yuan Jiang; Xian-Lei Fu (Waste Management, 2026)

Inhibition of Listeria monocytogenes biofilm formation by phenyllactic acid in pasteurized milk is associated with suppression of the Agr system - Hong Chen; Mingli Bi; Shujun Li; Shujun Yang; Yiping Zhang; Lili Zhao; Xiaobing Jiang; Tao Yu (International Journal of Food Microbiology, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Enhanced microalgal-bacterial granulation via a novel two-stage strategy: initial Microthrix parvicella-induced limited filamentous bulking and subsequent hydrodynamic-phototrophic synergy - Mengting Li; Zhipeng Chen; Zhaoming He; Sheng Yu; Weican Shi; Qian Bi; Xiang Li; Jiaqi Hu; Shuang Qiu; Shijian Ge (Bioresource Technology, 2026)

Bacillus velezensis D103 enhances maize drought tolerance via ROS-scavenging and phenylpropanoid pathway activation - Yating Zhang; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Fangfang Yu; Bo Zhang; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; Ning Zhang; Bingxue Li (Plant Cell Reports, 2026)

Myeloid Irf5 Deficiency Enhances the Therapeutic Efficacy of IMD-0354 in a TDP-25-Induced Neurodegeneration Model - Yuanyuan Li; Yuan Zhou; Lishuang Yu; Yue Bi; Le Yi; Chunyan Li; Yakun Liu (Molecular Neurobiology, 2026)

Flow and heat transfer characteristics of 3 × 3 rod bundles in natural circulation loop with asymmetrical inclination - Qiang Lian; Jing-Liang Bi; Si-You Yin; Yu Liang; Qi Lu; Lu-Teng Zhang; Liang-Ming Pan (Annals of Nuclear Energy, 2026)

The role and mechanisms of vitamin A in suppressing hepatic stellate cell activation - Wen Jia; Nannan Zhang; Daijiang Liu; Pengxiang Yu; Tao Lei; Yun He; Yang Bi (Apoptosis, 2026)

Multiple atmospheric drivers linked to the sea ice export out of the Arctic Ocean - Zheng Yu; Mengqi Hu; Lijun Ma; Haibo Bi (Acta Oceanologica Sinica, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

High-precision tobacco phenotype extraction based on 3D point clouds - Jiarui Chen; Jie Liu; Kangjie Ding; Linggai Cao; Jie Zhang; Zhixiao Yang; Haiming Xu; Weihong Bi; Shizhou Yu (Computers and Electronics in Agriculture, 2025)

3D LiDAR-based crop row detection for soybean at maturity under different planting densities - Wenbo Fang; Chunguang Bi; Jing Zhou; Helong Yu; Ming Zhao (Computers and Electronics in Agriculture, 2025)

Presence and sources of antibiotics in Dongzhai Harbor, Hainan Island - Tuan-Tuan Wang; Hong-Jin Zhang; Tuan-Qi Guo; Jia-Yu Luo; Bi-Jiao Li; Wen-Qing Liao; Ling Mo; Sai Wang; Yue-Hua Huang (Marine Pollution Bulletin, 2025)

Tea varieties modulate rhizosphere microbiome assembly via root metabolite-mediated selection - Litao Sun; Jiazhi Shen; Huan Wang; Yujie Song; XiaoJiang Li; Caihong Bi; ShuangShuang Wang; Xiuxiu Xu; Yu Wang; Zhaotang Ding (Rhizosphere, 2025)

The influence of temperature on the process of carbon dioxide fixation in sintered red mud and the mechanism of mineral phase evolution - Hao Zeng; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Mingxuan Shen (Journal of Environmental Chemical Engineering, 2025)

Enhancing anaerobic methane production from corn straw: Promoting lignocellulosic biomass biodegradation via aeration in liquid fraction of digestate for green and efficient pretreatment - Bi-Long Chen; Ting-Ting Zhang; Aqsa Arooj; Cheng Xu; Jia-Cheng E. Yang; Mika Sillanpää; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Colorimetric/fluorescent/photothermal multi-model sensor array based on the nanozyme for differentiating tea polyphenols and white tea vintages - Xiaoyu Yang; Jie Li; Zhichun Bi; Yu Gu; Yongxin Li; Hui Huang (Food Research International, 2025)

Valorization and evaluation of acidic and neutral polysaccharides from Panax ginseng processing residues for the mitigating effects on skin aging - Boyu Xiong; Rui Liu; Xinyi Zhi; Yanru Li; Jiameng Sun; Kaixuan Mao; Lei Yu; Yunfeng Bi (Food Research International, 2025)

Experimental investigation of effects of clay content on wave-induced failure of loosely-deposited submarine slopes - Yandong Bi; Shu Zhou; Xiaolin Tan; Zhen Guo; Chongqiang Zhu; Jin Sun; Yu Huang (Engineering Geology, 2025)

Phospholipid-inspired underwater adhesives achieving fast, durable, and harsh-condition bonding - Xiaoqian Bi; Shaoyu Luo; Zhenxuan Liang; Wenfan Yu; Junfang Xue; Shifeng Zhang; Anmin Huang; Songwu Chen (Chemical Engineering Journal, 2025)

Polyimide sulfonyl group grafting and POSS crosslinking designs depress multi-scales charge transport for high-temperature capacitive energy storage - Zhen Li; Qianyi Fan; Yikun Dong; Xuefei Bi; He Gao; Yu Feng; Ji Liu (Chemical Engineering Journal, 2025)

Interface-enhanced CO2-to-C2+ electroreduction via magnesium-regulated PVP nanospheres confining Cuδ+ active sites - Haozhong Yuan; Yuan Zhuang; Senyao Meng; Renlong Ma; Kaixuan Wei; Guiwu Lu; Huiting Hu; Xing Zhou; Ying Cui; Tieyin Zhang; Zhixiang Zeng; Tianteng Yu; et al. (Chemical Engineering Journal, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Balancing water efficiency and crop productivity: rhizosphere microbiome shifts in drought-resistant rice - Junguo Bi; Jiayi Li; Saeed ur Rahman; Yuchong Long; Nan Hui; Martin Romantschuk; Junqiang Zheng; Xianxian Zhang; Danping Hou; Jinsong Tan; Qingyu Bi; Hui Xia; et al. (World Journal of Microbiology and Biotechnology, 2025)

Specnuezhenide mitigates tunicamycin-induced liver injury in mice via ER stress modulation and metabolic reprogramming - Tianle Zhang; Dan Bi; Jiahui Li; Xin Jin; Huijuan Wu; Changyuan Yang; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Molecular Biology Reports, 2025)

Study on remaining useful life prediction of sliding bearings in nuclear power plant shielded pumps based on nearest similar distance particle filtering - Hang Wang; Shuaishuai Wu; Fangxiaozhi Yu; Yanchao Bi; Zhao Xu (Annals of Nuclear Energy, 2025)

Optimizing of random forest algorithm to analyze the spatiotemporal heterogeneity of urban resident carbon emissions in China - Jixiang Zhang; Yu Zhao; Sui Li; Xiaoyang Duan; Panpan Wang; Tianping Bi (Environment, Development and Sustainability, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Warm-dry climate narrowed the difference between vegetation greenness and photosynthetic phenology periods in the Yellow River Basin, China - Yan Liu; Jialin Bi; Xiaoyu Cai; Liping Wang; Guoqing Li; Xiaohui Wang; Xianbin Liu; Zhanpeng Xu; Xiang Yu; Chao Zhan (Remote Sensing Applications: Society and Environment, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

The mechanisms of vortex in tubular flame combustion and the impact on emissions - Jing-hao Zhang; Ming-shu Bi; Ting-ting Wu; Xing Liu; Di Yu; Yuan Wang; Jing-jie Ren (Journal of Cleaner Production, 2025)

Circ-379-miR-3050-DNAH3/RNF8 axis modulates wing development in Aphis citricidus - Yu-Jing Liu; Jin-Ming Lu; Xiu-Cheng Xie; Qin-Qin Xu; Bi-Yue Ding; Jin-Jun Wang; Feng Shang (Insect Biochemistry and Molecular Biology, 2025)

A mechanistic perspective: How does tert-butylhydroquinone retain antioxidative efficacy in edible oils during storage? - Mengqi Xu; Yaxing Yu; Jun Li; Yanlan Bi; Jun Liu; Chenyu Fu (Food Chemistry, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Lightweight and high-strength wood composite with asymmetric structure design - Shaoyu Luo; Zhenxuan Liang; Xiaoqian Bi; Wenfan Yu; Jinbo Wang; Zhili Xu; Shifeng Zhang (Chemical Engineering Journal, 2025)

Boosting power output of NH3BH3 fuel cell by modulating H* and OH− adsorption via Cu@Pd core-shell structured nanowire arrays - Shuo Bi; Libo Zhu; Han Tian; Fantao Kong; Xu Yu; Qin Li; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Amine-functionalized polysiloxane-engineered cellulose foam with Ag/MnO2 schottky interfaces for synergistic adsorption-photocatalytic formaldehyde elimination - Wenfan Yu; Shaoyu Luo; Zhenxuan Liang; Wentao Liu; Xiaoqian Bi; Shifeng Zhang; Taiquan Jin (Carbohydrate Polymers, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Revisiting the Indium Window effect: Insights from sphalerite big data - Qi-Nan Zou; Yu-Miao Meng; Rui-Zhong Hu; Xiao-Wen Huang; Xian-Wu Bi; Tai-Ping Zhao (Journal of Asian Earth Sciences, 2025)

Development of electrospun nanofiber membranes based on ZIF-8 MOF loaded tea polyphenols with pH-responsive release capabilities for food preservation - Yu Ma; Xinjian Zhang; Junjie Li; Zhichun Bi; Jie Li; Zhenglong Ma; Hui Huang; Yongxin Li (Innovative Food Science & Emerging Technologies, 2025)

The facile discriminative detection of four synthetic antioxidants in edible oil by a multi-signal sensor array based on the Bop-Cu nanozyme combining machine learning - Xinyue Zhang; Linxue Zhen; Zhichun Bi; Peize Jin; Yu Ma; Yongxin Li; Hui Huang (Food Research International, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Dissimilatory nitrate reduction to ammonium pathway during composting: Insight into key factors, functional microbes, and multi-factor interactions - Shuai Shi; Jiaxin Bao; Donghui Lv; Yonghui Xu; Zhiheng Guo; Jingjie Zhang; Shuai Ren; Yue Han; Ruixin Bi; Nana Jiang; Ning Wang; Jie Pan; et al. (Chemical Engineering Journal, 2025)

Achieving spatially separated photo-redox sites via COFs-based inorganic-organic S-scheme heterojunction for boosting solar ammonia production - Mingfei Yu; Yueling Chen; Xiaoping Song; Qiaoshan Chen; Liuyi Li; Jinhong Bi (Chemical Engineering Journal, 2025)

Tailoring sponge-like nitrogen-enriched biochar: A green and sustainable remediation technology for Pb and Cu contaminated soil - Jianhua Qu; Rui Yu; Mengning Wang; Nanfang Wang; Fuxuan Bi; Hang Gao; Chang Qin; Yifan Wang; Ying Zhang (Chemical Engineering Journal, 2025)

Ti3C2Tx/TiO2/CuO nanocomposite-based gas sensors for high-performance ethanol detection at room temperature - Ming Zhou; Xuefeng Hu; Zhiyuan Liu; Weiwei Qin; Liping Tan; Jilei Yang; Debao Yu; Qingqing Mu; Anquan Bao; Yali Bi; Wenjuan Yu; Wei Zhang (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Enhancement of high-solid chicken manure anaerobic digestion: Insights into ammonia air stripping pretreatment for microbial resilience and hydraulic retention stabilization - Xinhui Yu; Fangtong Wei; Haipeng Wang; Shaojie Bi; Changjiang Zhao; Yanjie Wang (Biomass and Bioenergy, 2025)

Transcriptomic Analysis Reveals Key Regulatory Genes and Pathways Involved in Macrophage Inflammation Induced by Hypervirulent Klebsiella pneumoniae Infection - Jinli Bi; Xin Huang; Liqin Meng; Jinghan Li; Yu He; Jing Jin; Taijie Li (Current Microbiology, 2025)

Emerging role of RNA m6A modifications in laryngeal squamous cell carcinoma: insights into tumorigenesis and therapeutic potential - Guotong Zheng; Jing Bi; Yangyan Yan; Bo Yu; Yong Fu (Apoptosis, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Research on the effects of split injection on diesel engine spray impingement and fuel film under cold-start conditions - Jie Yan; Luxin Fu; Weizheng Zhang; Xu He; Shuang Jin; Zhenyao Guo; Huahong Yu; Sinan Bi (Fuel, 2025)

Crocin alleviates high-sugar diet-induced type 2 diabetes model in Drosophila - Shichao Yu; Xue Lei; Shuting Meng; Xinyan Teng; Guanhua Yue; Jiahua Zhu; Bing Bi; Li Hua Jin (Food Bioscience, 2025)

Synergistic cytotoxicity of deoxynivalenol and nivalenol at realistic dietary exposure ratios through ribotoxic stress-induced apoptosis in Caco-2 cells - Su Been Park; Yu-Bi Choi; Sang Yoo Lee; Hyang Sook Chun (Food and Chemical Toxicology, 2025)

Loperamide-induced constipation is associated with excessive accumulation of bile acids and cholesterol in the liver of mice; attenuation by hesperidin - Jiahui Li; Dan Bi; Ya Nie; Huijuan Wu; Yuting Lei; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Food and Chemical Toxicology, 2025)

Bioengineered multifunctional hydrogel integrating oxygen sustention, oxidative stress alleviation and pro-angiogenic cues for regenerative MI therapy - Zhigao Song; Zhu Dong; Xuefei Yu; Yaling Li; Yizhou Bai; Longbao Feng; Guibin Qiao; Xiaowu Wang; Shenghui Bi (Chemical Engineering Journal, 2025)

Construction of multilayer multifunctional hydrogel microspheres with natural macromolecules, tannic acid, and copper for enhanced diabetic wound healing - Zuhan Chen; Beizhi Jiang; Huanjing Bi; Chongfeng Wang; Yanyan Liu; Jingwen Wang; Ying Wang; Zejiaxin Niu; Ruiyang Ma; Boqing Dong; Xiaoyang Yu; Fang Xie; et al. (Chemical Engineering Journal, 2025)

Revealing the ionic storage mechanisms of Mo2VC2Tz (MXene) in multiple aqueous electrolytes for high-performance supercapacitors - Xiaodie Xuan; Yangyang Xie; Yi Tang; Jianghong Zhou; Zhao Bi; Junhui Zou; Yu-ang Lei; Jiahang Gao; Lu Li; Aibo Zhang; Chenhui Yang (Chemical Engineering Journal, 2025)

Improve furfural production from lignocellulosic biomass using Zn/MgAl2O4 catalyst - Zhaojie Qin; Dongmei Bi; Bozheng Li; Xiang Zhu; Yu Ni; Lihong Wang (Biomass and Bioenergy, 2025)

A Semianalytical Elastoplastic Hydraulic‒Mechanical Model for Tunnel Surrounding Rock in the Excavation Damaged Zone - Yu Zhao; Tao Wei; Chaolin Wang; Jing Bi; Shuang Dang; Mingxuan Shen (Rock Mechanics and Rock Engineering, 2025)

Discrimination of tea varieties and bud sprouting phenology using UAV-based RGB and multispectral images - Litao Sun; Jiazhi Shen; Yilin Mao; Xiaojiang Li; Kai Fan; Wenjun Qian; Yu Wang; Caihong Bi; Hui Wang; Yang Xu; Jingbiao Xu; Zhaotang Ding (International Journal of Remote Sensing, 2025)

Southward subduction of the Mongol–Okhotsk Ocean: constraints from Late Triassic granites in the Hailar Basin, NE China - Zhikun Dai; Zheng Ji; Qian Meng; Chuanbiao Wan; Wenjing Bai; Hao Yang; Junhui Bi; Wei Huang; Yongzhi Wang; Yu Dong; Wenchun Ge (International Geology Review, 2025)

Energy Decomposition-Driven Design of Trop2-Targeting Peptide - Yu-Chao Meng; He Liu; Bi-Shao Sun; Hong-Yuan Liu; Hong-Wei Li; Qiu-Yu Liao; Mouxin Huang; Qin Ouyang (Cell Biochemistry and Biophysics, 2025)

A new triterpenoid saponin and a new natural saponin from the roots of Bupleurum scorzonerifolium willd - Zi-Wei Li; Jia-Tong Wu; Yu Bi; Meng-Meng Li; Anam Naseem; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Yan Liu; et al. (Natural Product Research, 2025)

Photodegradation mechanism of organic contaminants mediated by chlorinated algal organic matter - Dong Wan; Chengjie Yu; Yafei Zhao; Gaofei Song; Wujuan Mi; Yuxuan Zhu; Changzi Liu; Yonghong Bi (Water Research, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Prediction of shear characteristics at core pile-cemented soil interface for offshore wind turbine pile foundation based on machine learning - Yu-liang Yan; Yu-xi Zeng; Yong-chao Liu; Bing-bing Li; Xiu-feng Liu; Bi-sheng Xu (Ocean Engineering, 2025)

Solidifying/stabilizing soluble manganese and ammonia nitrogen in electrolytic manganese residue via the hydrolysis of dicalcium silicate in magnesium slag - Wei Tang; Mingxuan Shen; Yu Zhao; Yong Li; Chaolin Wang; Juhong Yang; Qian Cao; Jing Bi; Yongfa Zhang; Houqin Wu; Junxin Liu (Journal of Hazardous Materials, 2025)

Efficient dual broadband VIS-NIR emission in Mo-doped double perovskites enabling detection and imaging applications - Xin Li; Jinming Yan; Liang Wang; Lanbo Shen; Feng Jiang; Fujun Zhang; Jiayi Xu; Qilin Wei; Tong Chang; Zilong Wu; Terefe Tafese Bezuneh; Xue Bai; et al. (Chemical Engineering Journal, 2025)

Bisulfite-free whole-genome mapping of 5-methylcytosine at single-base resolution by NTD-seq - Min Wang; Neng-Bin Xie; Fang-Yin Gang; Shan Zhang; Li Zeng; Tong-Tong Ji; Jun Xiong; Xia Guo; Ying Hao; Yu Liu; Bi-Feng Yuan (Science China Life Sciences, 2025)

Exploring mechanisms of radiation-induced myocardial fibrosis using HMGB1 neutralizing antibody - Gang Wang; Bi-Bo Wu; Sha-Sha Zhao; Jing Zhang; Yu Wang; Yin-Xiang Hu; Jun Wan; Bing Lu; Sheng-Fa Su (Journal of Molecular Histology, 2025)

Identification of gut microbiota causally associated with aging and longevity and mediation roles of the cerebrospinal fluid proteins: proteomic genetic evidence from Mendelian randomization - Ruonan Liu; Zheng Zhu; Yuanyue Zhu; Xin Lin; Hongjie Li; Tiange Wang; Jie Zheng; Mian Li; Zhiyun Zhao; Yu Xu; Jieli Lu; Weiqing Wang; et al. (GeroScience, 2025)

The GLI3 may be involved in the damage process of Eimeria tenella to chicken cecal tissue - Wanjiang Xiang; Ying Chen; Ye He; Yongmei Yu; Ping Li; Bi Wang; Zhentao Cheng (Veterinary Parasitology, 2025)

Probabilistic evaluation of enterprises' fraudulent report in pollutant levels based on machine learning: a case of hazardous waste generation quantity - Wen Fang; Qingyuan Yu; Wenjun Xie; Jianxun Yang; Zongwei Ma; Miaomiao Liu; Jun Bi (Resources, Conservation and Recycling, 2025)

The cell death-inducing protein BcPlp1 from Botrytis cinerea contributes to pathogenicity and modulates plant resistance - Xiaofei Nie; Ziyao Wang; Binbin Huang; Qiongnan Gu; Ran Xu; Shuang Yu; Chao Xiong; Zhiguo Liu; Wei Wei; Kai Bi; Wenjun Zhu (Plant Science, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Construction of 2D-2D heterojunctions of VN nanosheets within Ti3C2 nanosheets for improved flow-electrode capacitive deionization performance - Kang Yang; Wei-Bin Zhang; Juan Zhou; Huan Gou; Ashkar Batol; Fan Yang; Bi Chen; Xin-Yu Liu; Xue-Jing Ma (Desalination, 2025)

Co-pyrolysis of polyurethane and biomass: Piperidine derivative production and nitrogen mechanism modulation by flame retardants - Yu Ni; Dongmei Bi; Shuangshuang Yan; Hui Wang; Chunwang Dong; Shanjian Liu (Chemical Engineering Journal, 2025)

Synthetic biology-enabled, biodegradable, performance-tunable and melt-processable bioplastics - Tianhua Ren; Yanqi Bi; Jialong Li; Jinlin Li; Dongdong Gao; Feng Yu; Jingyu Wang; Kechun Zhang (Chemical Engineering Journal, 2025)

Bioactive multifunctional hydrogel to ameliorate adverse joint microenvironment and enhance cartilage regeneration - Zhang Po; Ma Xiao; Zhang Han; Liu Yang; Zhu Liang; Bi Yanchi; Wang YiHu; Shen Zhan; Wang Jian; Jiang Fan; Zhu Xuesai; Yao Yizhi; et al. (Chemical Engineering Journal, 2025)

Investigation of Microwave Heating on Sandstone Subjected to Liquid Nitrogen Freeze–Thaw: Permeability Evolution Mechanism - Zairong Yang; Chaolin Wang; Yu Zhao; Jing Bi (Rock Mechanics and Rock Engineering, 2025)

MiR-124 Delivered by Extracellular Vesicles from Mesenchymal Stem Cell Exerts Neuroprotective Effects by Stabilizing the p62-Keap1-Nrf2 Pathway after Spinal Cord Injury in Rats - Chao Fang; Jun Qian; Bi-zhi Tu; Xiang Xia; Chong-yu Jia; Cai-liang Shen (Molecular Neurobiology, 2025)

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Uncovering horizontal and vertical inequities of individual accessibility using mobile phone data - Jinmeng Zhang; Bi Yu Chen; Chenxi Fu; Zehao Yuan; Donggen Wang (Transportation Research Part D: Transport and Environment, 2025)

Oxygen/sulfate radicals-generating CaS2O8 nanosonosensitizers induce PANoptosis and calcium overload for enhanced peritoneal metastasis immunotherapy - Qiang Wang; Yingfei Wen; Bo Bi; Kuan Li; Yuanqi Liu; Binbin Li; Shangbo Zhou; Zihang Li; Jiaqi Xu; Miaojuan Qiu; You Li; Meiying Wu; et al. (Science Bulletin, 2025)

Unraveling the degradation mechanism of nitrobenzene in excess oxygen triggered by HO• from DFT and kinetic insights - Yufeng Wu; Runlai Ji; Zongyi Yu; Mingshu Bi; Dongcheng Yang (Process Safety and Environmental Protection, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Aptamer-modulated Pt/Au/MIL-100(Fe) nanozymatic activity for the colorimetric detection of deoxynivalenol in grains - Huang Dai; Junlan Yu; Run Zhou; Guijie Hao; Zhaohui Qiao; Zhe Feng; Xin Liu; Jie Bi; Jiahua Wang; Xiaodan Liu; Fuwei Pi; Yafang Shen (Food Chemistry, 2025)

A starch-like polysaccharide isolated from Hirsutella sinensis mycelia alleviates DSS-induced colitis in mice by strengthening the intestinal barrier, maintaining immune homeostasis, and modulating the gut microbiota and SCFA metabolism - Yu Li; Hailiang Wang; Hongtao Bi; Jingyue Feng; Tingting Gao; Dai Dong; Guoqiang Li; Boxuan Liu; Hongyan Yuan; Weihua Ni (Food Bioscience, 2025)

The effects of clay content on the dynamics of submarine landslides: New insights from flume experiments - Shu Zhou; Yandong Bi; Xiaolin Tan; Jian Pu; Zhen Guo; Chongqiang Zhu; Jin Sun; Yu Huang (Engineering Geology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Boosting electrochemical activity via manipulating the d-band center of CoNi2Se4/MXene heterostructure for supercapacitor application - Minmin Hu; Lihong Chen; Yu Wang; Jun Dai; Yifan Bi; Yuanming Li; Jian Zhao; Guicun Li; Lei Wang; Alan Meng; Zhenjiang Li (Chemical Engineering Journal, 2025)

Flotillin- 1 ameliorates experimental diabetic retinopathy by inhibiting ferroptosis in blood-retinal barrier - Jie Zhang; Ke Chang; Yanyu Shangguan; Ruoning Luo; Yanlong Bi; Zicheng Yu; Bing Li (Journal of Molecular Medicine, 2025)

Load Characteristics of a Large Double-Arch Tunnel in Weak Fly Ash Deposits - Lang Bi; Junfeng Sun; Zhigang Yao; Tao Yu; Yong Fang; Xiwen Li; Laibin Ye (Geotechnical and Geological Engineering, 2025)

Experimental study of the development process and hazard scope of horizontally oriented liquefied gases jet fires - Qiangqiang Hao; Mingshu Bi; Di Yu; Jianlei Zhang; Xin Lei; Zilong Deng; Jingjie Ren (Fuel, 2025)

Metabolomic analysis elucidates the dynamic changes in aroma compounds and the milk aroma mechanism across various portions of tea leaves during different stages of Oolong tea processing - Bi-Heng Wang; Ping-Hsiu Huang; Chih-Yu Lo; Wen-Chang Chang (Food Research International, 2025)

Three-channel Sensor Array based on Switchable Nanozymatic Reactions of a Novel Trimetallic Nanozyme for Anti-interference Identification of Tea Adulteration - Jie Li; Linxue Zhen; Zhichun Bi; Yu Ma; Hui Huang; Yongxin Li (Chemical Engineering Journal, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Revealing the Effect of Pore Size Distribution Characteristics on Macroscopic Properties of Red Sandstone Under Instantaneous High Temperature Through the Lens of Shannon Entropy Theory - Lin Ning; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang; Yang Li; Yuhang Zhao; Xiaojiang Deng (Rock Mechanics and Rock Engineering, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Offspring number and composition influence parental care strategy and offspring survival in the azure-winged magpie - Bi-Yun Jia; Zhen-Qin Zhu; Wen-Jing Zhu; Yu-Jie Wang; Ning-Ning Sun; Bo Du (Animal Behaviour, 2025)

Experimental study on explosive boiling mechanism of horizontal vessels - Jingjie Ren; Xing Liu; Zilong Deng; Qiangqiang Hao; Di Yu; Jianlei Zhang; Shaochen Sun; Mingshu Bi (Process Safety and Environmental Protection, 2025)

Glyphosate combined with TBBPA exposure decreased quality and flavor of common carp (Cyprinus carpio) involved inhibiting muscle growth and collagen synthesis - Dongxu Han; Yanju Bi; Tingting Yu; Xuewei Chen; Shiwen Xu (Pesticide Biochemistry and Physiology, 2025)

Implications of the different submerged extent of typical sandbars to local DOM and SDOM during the pre-flood season in the middle reaches of Yangtze River - Haoyang Shi; Hui Guo; Wenjun Yang; Chengcheng Bao; Xinxin Zhu; Sheng Bi; Yu Hu; Ting Li (Journal of Environmental Management, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Study on the effect of multistage A/O-MBBR pilot system on urban sewage treatment: Removal contribution and microbial community changes - Qingyang Bi; Xiaowan Dong; Jicheng Duan; Fangshu Wang; Shixin Yu; Lihua Cheng; Xuejun Bi; Dong Chen (Journal of Environmental Chemical Engineering, 2025)

Microwave-assisted synthesis and functionalization of biochar for environmental remediation: Regulate strategy and application potential - Jianhua Qu; Rui Yu; Xiaoyang Liu; Wei Peng; Fuxuan Bi; Xu Liu; Qiwen An; Yupeng Zhang; Qi Hu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Melatonin promoted terpene accumulation of blueberries during postharvest partial dehydration - Qin Yang; Hai-Jun Bi; Qi Zhang; Chen Bian; Lu-Lu Zhao; Shu-Qin Huang; Jun Jiang; Hong-Bing Chen; Xue-Ling Gao; Yu Wang (Food Chemistry, 2025)

Highly efficient enzymatic enrichment of n-3 polyunsaturated fatty acid glycerides via interfacial biocatalysis in Pickering emulsions - Liumei Wu; Dongming Li; Fuyang Bi; Chao Yu; Yufei Zhang; Mingming Zheng (Food Chemistry, 2025)

Chemical profiles and mechanisms insights into Liuwei Dihuang-based formulas in diabetic nephropathy treatment: An integrated transcriptomics with in vitro experiments - Yanxia Liu; Anlei Yuan; Zewen Wang; Shijie Bi; Zhenzhen Xu; Chaoqun Liu; Bin Yu; Jiaye Tian; Liansheng Qiao; Zhaozhou Lin; Jun Jia; Yanling Zhang (Food Bioscience, 2025)

Metatranscriptomics reveals that plant tannins regulate the expression of intestinal antibiotic resistance genes in Qinghai voles (Neodon fuscus) - Shunqin Shi; Xueying Gan; Yuan Qian; Yiming Cao; Yu Wang; Chenwei Shi; Jie Bi; Qiaoling Yu; Qian Han; Jiapeng Qu; Huan Li (Environmental Research, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Corrigendum to “Machine learning assisted biomimetic flexible SERS sensor from seashells for pesticide classification and concentration prediction” [Chem. Eng. J. 507 (2025) 160813] - Yu Wan; Qian Wei; Hao Sun; Hanzhaobing Wu; Yimin Zhou; Changwei Bi; Jitao Li; Lili Li; Bin Liu; Dalei Wang; Chaoqing Dai; Xiaoyan Wang; et al. (Chemical Engineering Journal, 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Ultrasensitive CEA detection using SiO2/AuNPs-mediated dual inhibition in a signal-off-type photoelectrochemical immunosensor - Yueyuan Cai; Zhaoshun Bi; Xinming Geng; Jingtian Chi; Ming Gao; Youchang Liu; Zhilei Qiu; Xiaoyue Zhang; Liangmin Yu; Zhi Chen; Wei Shan; Meng Qiu (Analytica Chimica Acta, 2025)

Nanoconfined in-situ sampling and extracting switching needle device construction for highly enrichment of polar metabolites in human urine - Chunyu Yu; Yifan Jiao; Lang Bi; Yilin Zou; Jinhua Zhao; Meihui Tong; Xiaohan Zong; Jiaxin Zhang; Songnan Zhang; Donghao Li (Analytica Chimica Acta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

A new feature selection algorithm combining genetic algorithm, exponential decay function, and machine learning to realize hyperspectral estimation of winter wheat leaf area index - Chenbo Yang; Juan Bai; Hui Sun; Rutian Bi; Lifang Song; Amjad Muhammad; Chao Wang; Yu Zhao; Wude Yang; Lujie Xiao; Meijun Zhang; Xiaoyan Song; et al. (Computers and Electronics in Agriculture, 2025)

Functional potential of compound probiotics fermented soybean meal partially replacing fish meal in spotted seabass (Lateolabrax maculatus): Insights through growth, immunity, antioxidant capacity and intestinal health - Bi-Yun Zhang; Ze-Hui Yuan; Hai-Xia Yu; Hong-Ling Yang; Guo-He Cai; Chun-Xiao Zhang; Jie Su; Yun-Zhang Sun (Aquaculture, 2025)

Experimental and theoretical study of nickel removal by electrodeposition on RVC-M (M=Cu, Fe, Mn) cathode - Yihong Sun; Jianfeng Wan; Wenyan Bi; Shizheng Xie; Menglin Yu; Yikai Hou; Tianen Li; Dongkui Zhou; Lebin Li; Baozhong Liu (Process Safety and Environmental Protection, 2025)

Comprehensive analysis of transplacental transfer of environmental pollutants detected in paired maternal and cord serums - Ke-Yu Yuan; Yao-Hua Gu; Yi-Hao Pei; Si-Yu Yu; Tian-Zhou Li; Tian Feng; Yu Liu; Jianbo Tian; Xiaoping Miao; Jun Xiong; Min Hu; Bi-Feng Yuan (Journal of Hazardous Materials, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

The optimized nitrogen rate reduced ammonia emissions from rice paddies in the cold region of Northeast China - Shiting Bi; Pengfei Li; Jiarui Lv; Qiang Dong; Xiangyu Luo; Yeqi Che; Muhammad Rehman Naseer; Zhilei Liu; Cailian Yu; Xianlong Peng (European Journal of Agronomy, 2025)

Role of initial particle deposition in collapse dynamics and deposition morphology of submarine granular flows using CFD-DEM coupling method - Yu Huang; Xiaolin Tan; Yandong Bi; Shu Zhou; Jian Pu; Zhen Guo (Engineering Geology, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

Machine learning assisted biomimetic flexible SERS sensor from seashells for pesticide classification and concentration prediction - Yu Wan; Qian Wei; Hao Sun; Hanzhaobing Wu; Yimin Zhou; Changwei Bi; Jitao Li; Lili Li; Bin Liu; Dalei Wang; Xiaoyan Wang; Chao Wang; et al. (Chemical Engineering Journal, 2025)

A novel win–win wastewater treatment process: Recover functional element from sludge to enhances TiO2 for deep photocatalytic oxidation - Bo Sun; Yu Tian; Menglin Feng; Sihan Zhang; Hong Yang; Junmei Qin; Wenlong Bi; Xingxing Qiao; Fenwu Liu; Qingjie Hou (Chemical Engineering Journal, 2025)

Regulating the macroscopic and microscopic self-assembly behavior of hydroxybutyl chitosan based on alkyl distribution - Shichao Bi; Guohui Sun; Tianrui Wang; Di Qin; Qiang Yu; Xiao Ma; Houxi Li; Xiguang Chen; Bo Tang (Carbohydrate Polymers, 2025)

Multi-performance coupled optimization drives low-carbon retrofitting of site museums - Shanshan Yao; Shugang Yu; Hu Cao; Wenbei Bi; Jiamin Zhang; Duo Zhang; Jingpeng Fu; Pingan Ni (Building and Environment, 2025)

Single-Neuron Reconstruction of the Macaque Primary Motor Cortex Reveals the Diversity of Neuronal Morphology - Siyu Li; Yan Shen; Yefei Chen; Zexuan Hong; Lewei Zhang; Lufeng Ding; Chao-Yu Yang; Xiaoyang Qi; Quqing Shen; Yanyang Xiao; Pak-Ming Lau; Zhonghua Lu; et al. (Neuroscience Bulletin, 2025)

MMP13 as an effective target of an active trifluoromethyl quinazoline compound against osteosarcoma - Chang-hua Zhou; Ting Zhang; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Bi-xue Xu; Heng Luo; Xiao-bin Tian (Toxicology and Applied Pharmacology, 2025)

Multi-scale urban ecosystem service changes and their impact mechanisms on human well-being - Jia Bi; Minghao Lu; Fengchen Liu; Yimeng Cai; Yijun Wang; Minjie Duan; Jiale Li; Xinyu Li; Deyong Yu (Journal of Environmental Management, 2025)

Understanding the impacts of ecological compensation policy on rural livelihoods: Insights from forest communities of China - Yuan Gao; Yingjie Bi; Lu Yu (Journal of Environmental Management, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Improving sugar and respiratory metabolism in pear wounds by postharvest dipping with chitosan and chitooligosaccharide - Lirong Yu; Xuemei Zhang; Pengdong Xie; Tingting Su; Wei Liang; Yi Wang; Dov Prusky; Gianfranco Romanazzi; Yang Bi (Food Chemistry, 2025)

Neutral oligosaccharides from ginseng (Panax ginseng) residues vs. neutral ginseng polysaccharides: A comparative study of structure elucidation and biological activity - Li Tao; Jingwei Zhang; Wenfei Lan; He Liu; Qi Wu; Shenglong Yang; Shixin Song; Lei Yu; Yunfeng Bi (Food Chemistry, 2025)

Nitrogen-doped porous hydrochar for enhanced chromium(VI) and bisphenol A scavenging: Synergistic effect of chemical activation and hydrothermal doping - Jianhua Qu; Fansong Meng; Fuxuan Bi; Zhao Jiang; Mengning Wang; Qi Hu; Yupeng Zhang; Hui Yu; Ying Zhang (Environmental Research, 2025)

Charged defect management for high-efficiency planar solar cells: Reducing charge recombination and open-circuit voltage loss by employing donor-acceptor molecules to regulate perovskite electronic properties - Miao Yu; Lin Fan; Lixue Wang; Chuanlong Bi; Yuan Gao; Jiadong Liu; Fengyou Wang; Xin Li; Qiong Wu; Xiaoyan Liu; Huilian Liu; Lili Yang (Chemical Engineering Journal, 2025)

IsoVISoR: Towards 3D Mesoscale Brain Mapping of Large Mammals at Isotropic Sub-micron Resolution - Chao-Yu Yang; Yan Shen; Xiaoyang Qi; Lufeng Ding; Yanyang Xiao; Qingyuan Zhu; Hao Wang; Cheng Xu; Pak-Ming Lau; Pengcheng Zhou; Fang Xu; Guo-Qiang Bi (Neuroscience Bulletin, 2025)

Thermal Damage and Acoustic Emission Characteristics of High-Temperature Granite under Liquid Nitrogen Cooling - Yilei Yuan; Kun Zheng; Chaolin Wang; Yu Zhao; Jing Bi (Natural Resources Research, 2025)

Quercetin alleviates neonatal hypoxic-ischaemic brain injury by rebalancing microglial M1/M2 polarization through silent information regulator 1/ high mobility group box-1 signalling - Zhaoyan Chen; Fei Ruan; Di Wu; Xiaoping Yu; Yaqing Jiang; Wei Bao; Haicheng Wen; Jing Hu; Haidi Bi; Liping Chen; Kai Le (Inflammopharmacology, 2025)

Land-atmosphere feedback exacerbated the mega heatwave and drought over the Yangtze River Basin of China during summer 2022 - Xiao Chen; Jialin Wang; Feifei Pan; Yu Song; Ju Liang; Na Huang; Kang Jiang; Riping Gao; Jingyu Men; Pengshuai Bi; Fangxiao Zhang; Zhanrui Huang; et al. (Agricultural and Forest Meteorology, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Simulation study on the effect of temperature on hydrogen production performance of alkaline electrolytic water - Xiaobing Bi; Gan Wang; Daan Cui; Xinyi Qu; Shuaishuai Shi; Dong Yu; Mojie Cheng; Yulong Ji (Fuel, 2025)

A novel sensor array with ability to respectively identify phenol and ketone for the precise discrimination of origins of raw Pu-erh and its counterfeiting - Zhichun Bi; Linxue Zhen; Jie Li; Peize Jin; Yu Gu; Yu Ma; Donghui Song; Xiaoyu Yang; Yongxin Li; Hui Huang (Food Research International, 2025)

Nobiletin, an activator of the pyruvate kinase isozyme M1/M2 protein, upregulated the glycolytic signalling pathway and alleviated depressive-like behaviour caused by artificial light exposure at night in zebrafish - Meng-ling Zhang; Xiao-peng Li; Li-fang Gao; Jian Liu; Zi-jun Bi; Yu-han Miao; Yang Shan; Huan-ling Yu (Food Chemistry, 2025)

Differential mechanisms of Liuwei Dihuang pill-derived formulas in treating diabetic nephropathy based on in vitro experiments and transcriptomic analysis - Shijie Bi; Anlei Yuan; Zhenzhen Xu; Zewen Wang; Yanxia Liu; Bin Yu; Jiaye Tian; Chaoqun Liu; Liansheng Qiao; Zhibin Wang; Yanling Zhang (Food Bioscience, 2025)

Agricultural resource management strategies for greenhouse gas mitigation: The land-energy-food-waste nexus based on system dynamics model - Bo Yu; Xueqing Liu; Xuehao Bi; Hua Sun; Jeroen Buysse (Environmental Impact Assessment Review, 2025)

A new semi–analytical method for elastic–strain softening circular tunnel with hydraulic–mechanical coupling - Tao Wei; Chaolin Wang; Yu Zhao; Jing Bi; Yongfa Zhang (Engineering Geology, 2025)

Inspired by the tessellation of strawberry achenes on skin: Preparation of ZIF-67 derived multifunctional flame retardant through supramolecular assembly of cobalt alginate biopolymer in melamine-containing polyphosphazene skeleton - Qianlong Li; Yu Lei; Xue Bi; Yina Liu; Ye-Tang Pan; Wei Wang; Wenchao Zhang; Congling Shi; Guan Heng Yeoh (Chemical Engineering Journal, 2025)

Generation of unpaired electrons to promote electron transfer at the cathode of room-temperature sodium sulfur batteries - Chen Huang; Jing Yu; Yao-Jie Lei; Oleg Usoltsev; Li Gong; Zhibiao Cui; Junshan Li; Canhuang Li; Bingfei Nan; Xuan Lu; Ren He; Xuede Qi; et al. (Chemical Engineering Journal, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Acid-etched halloysite and Co-Ni-B composites for high-performance supercapacitor application - Fan Yang; Xue-Jing Ma; Jun-Hu Liu; Bi Chen; Kang Yang; Xin-Yu Liu; Wei-Bin Zhang (Applied Clay Science, 2025)

Influence of stearate dry coating on ibuprofen powder: What about the combustibility? - Tongtong Bian; Song Mei; Tianyang Zhang; Yuan Yu; Yajie Bu; Yuhang Bi; Zhangwei Huang; Qingwu Zhang; Tingting Chen; Zhongwei Chen; Juncheng Jiang (Process Safety and Environmental Protection, 2024)

Late Paleozoic–Early Mesozoic subduction history of Mudanjiang Ocean: New insights from greenschist in the Heilongjiang Complex, NE China - Simiao Wang; Yu Dong; Junhui Bi; Yan Jing; Wenchun Ge; Hao Yang; Jielu Yu; Zheng Ji (Lithos, 2024)

Research on chromium removal mechanism by electrochemical method from wastewater - Jianfeng Wan; Menglin Yu; Wenyan Bi; Yihong Sun; Wei Wang; Yikai Hou; Shizheng Xie; Tianen Li; Yunchang Fan (Journal of Water Process Engineering, 2024)

Co-management enhances social capital and recognition of protected area: Perspectives from indigenous rangers on the Qinghai-Tibet Plateau - Zhi Zhang; Yu Wei; Ling Tang; Zhi Wang; Xuetian Hu; Xinting Li; Yixing Bi; Baorong Huang (Journal of Environmental Management, 2024)

“Rigid-Flexible” structured polyimine/graphite felt composites with excellent fire Resistance, electromagnetic shielding and recyclability - Jue Wang; Hongliang Ding; Zhuyun Bi; Lu Liu; Na Sun; Wei Wang; Chuanshen Wang; Hongfei He; Keqing Zhou; Bin Yu (Chemical Engineering Journal, 2024)

MsDUF3700 overexpression enhances aluminum tolerance in alfalfa shoots - Jiamin Cao; Tingting Wang; Dian Yu; Junyi He; Wenwu Qian; Bingxia Tang; Xiaojing Bi; Hui Wang; Yunwei Zhang (Plant Cell Reports, 2024)

Mechanisms of intermittent theta-burst stimulation attenuating nerve injury after ischemic reperfusion in rats through endoplasmic reticulum stress and ferroptosis - Xin-Ya Shen; Xing-Yu Zhang; Ping-Ping Han; Yi-Ning Zhao; Guo-Hui Xu; Xia Bi (Molecular Biology Reports, 2024)
Background Repetitive transcranial magnetic stimulation (rTMS) exerts neuroprotective effects early in cerebral ischemia/reperfusion (I/R) injury. Intermittent theta-brust stimulation (iTBS), a more time-efficient modality of rTMS, improves the efficiency without at least decreasing the efficacy of the therapy. iTBS elevates cortical excitability, and in recent years it has become increasingly common to apply iTBS to patients in the early post-IS period. However, little is known about the neuroprotective mechanisms of iTBS. Endoplasmic reticulum stress (ERS), and ferroptosis have been shown to be involved in the development of I/R injury. We aimed to investigate the potential regulatory mechanisms by which iTBS attenuates neurological injury after I/R in rats. Methods Rats were randomly divided into three groups: sham-operated group, MCAO/R group, and MCAO/R + iTBS group, and were stimulated with iTBS 36 h after undergoing middle cerebral artery occlusion (MCAO) or sham-operated. The expression of ERS, ferroptosis, and apoptosis-related markers was subsequently detected by western blot assays. We also investigated the mechanism by which iTBS attenuates nerve injury after ischemic reperfusion in rats by using the modified Neurological Severity Score (mNSS) and the balance beam test to measure nerve function. Results iTBS performed early in I/R injury attenuated the levels of ERS, ferroptosis, and apoptosis, and improved neurological function, including mNSS and balance beam experiments. It is suggested that this mode of stimulation reduces the cost per treatment by several times without compromising the efficacy of the treatment and could be a practical and less costly intervention.

Environmental factors influencing the development and spread of resistance in erythromycin-resistant streptococcus pneumoniae - Zhi-Hua Sun; Yi-Chang Zhao; Jia-Kai Li; Huai-yuan Liu; Wei Cao; Feng Yu; Bi-Kui Zhang; Miao Yan (Environmental Geochemistry and Health, 2024)

Effects of alligator weed invasion on wetlands in protected areas: A case study of Lishui Jiulong National Wetland Park - Xiang-Hua Fang; Xuan-Ming Chen; Ri-Lin Liu; Si-Hai Zhang; Jun-Qin Gao; Bi-Cheng Dong; Fei-Hai Yu (Science of The Total Environment, 2024)

Predictive modeling of patulin accumulation in apple lesions infected by Penicillium expansum using machine learning - Xiaoyan Cheng; Rongxia Li; Pengdong Xie; Xuexue Wang; Lirong Yu; Ruofei Wu; Huali Xue; Yang Bi (Postharvest Biology and Technology, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Efficient PPCPs removal from wastewaters via a novel A/O-MBBR system: Transition towards circular economy in the water sector - Xiaowan Dong; Fangshu Wang; Shixin Yu; Jie Lan; Xing Fan; Xiaolin Zhou; Wei Wei; Guo Li; Lihua Cheng; Xuejun Bi; Ruibo Hu; Dong Chen (Journal of Environmental Management, 2024)

Enhanced deep-water circulation facilitated rare earth elements enrichment in pelagic sediments from the northwestern Pacific Ocean - Dongjie Bi; Xuefa Shi; Mu Huang; Fangyu Shen; Miao Yu; Ying Zhang; Fengdeng Shi; Jihua Liu (Global and Planetary Change, 2024)

Preharvest spraying of phenylalanine activates the sucrose and respiratory metabolism in muskmelon wounds during healing - Pengdong Xie; Yangyang Yang; Di Gong; Lirong Yu; Yi Wang; Yongcai Li; Dov Prusky; Yang Bi (Food Chemistry, 2024)

Evidence of polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs) in wild fish species from the remote tropical marine environment, south China sea - Run-Xia Sun; Chang-Gui Pan; Feng-Jiao Peng; Zi-Ling Yu; Hai-Yang Shao; Bing-Zhong Yang; Zhong-Biao Chen; Bi-Xian Mai (Environmental Pollution, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Drugs targeting TGF-β/Notch interaction attenuate hypertrophic scar formation by optic atrophy 1-mediated mitochondrial fusion - Da Huo; Xin-yu Bi; Jun-ling Zeng; Da-mao Dai; Xiang-lin Dong (Molecular and Cellular Biochemistry, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

Exploring the application and decision optimization of climate-smart agriculture within land-energy-food-waste nexus - Bo Yu; Xuehao Bi; Xueqing Liu; Hua Sun; Jeroen Buysse (Sustainable Production and Consumption, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influence of corrugated tube structure and flow rate on the hydrogen absorption performance of metal hydride reactor and structural optimization - Wenyan Bi; Yikai Hou; Jianfeng Wan; Jian Hu; Menglin Yu; Xiangxuan Xu; Yihong Sun; Qiang Zhou; Shizheng Xie; Tianen Li; Baozhong Liu (Process Safety and Environmental Protection, 2024)

3-ketoacyl-CoA synthase 7 from Xanthoceras sorbifolium seeds is a crucial regulatory enzyme for nervonic acid biosynthesis - Linkun Li; Chongjun Liang; Wei Zhang; Xin Zhang; Haiyan Yu; Xiaojuan Liu; Quanxin Bi; Libing Wang (Plant Science, 2024)

Coke oven emissions exacerbate allergic asthma by promoting ferroptosis in airway epithelial cells - Xian Chen; Hongguang Chen; Pimei Zhang; Qiang Ju; Zhaoxu Wu; Nuo Xu; Qing Bi; Shuaishuai Yang; Jing Ji; Dianke Yu; Yanjie Zhao (Journal of Hazardous Materials, 2024)

Anti-inflammatory action and associated intracellular signaling of Centella asiatica extract on lipopolysaccharide-stimulated RAW 264.7 macrophage - Hyun Young Shin; Yeon Suk Kim; Eun Ji Ha; Ja Pyeong Koo; Won Bi Jeong; Mi Yeun Joung; Kwang-Soon Shin; Kwang-Won Yu (Food Bioscience, 2024)

Oxygen-deficient NH4V4O10 cathode with Ag quantum dots and interlayer Ag+ towards high-performance aqueous zinc ion batteries - Yu Qiu; Zhihao Sun; Zihao Guo; Jingyu Bi; Guangshen Li; Lei Qian (Chemical Engineering Journal, 2024)

The Long Non-Coding RNA NR3C2-8:1 Promotes p53-Mediated Apoptosis through the miR-129-5p/USP10 Axis in Amyotrophic Lateral Sclerosis - Dejiang Pang; Yujiao Yu; Bi Zhao; Jingxuan Huang; Yiyuan Cui; Tengfei Li; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2024)
Motor neuron degeneration in amyotrophic lateral sclerosis (ALS) is a form of apoptosis, but the mechanisms underlying this neuronal cell death remain unclear. Numerous studies demonstrate abnormally elevated and active p53 in the central nervous system of ALS patients. Activation of p53-regulated pro-apoptotic signaling pathways may trigger motor neuron death. We previously reported decreased expression of the long non-coding RNA NR3C2-8:1 (Lnc-NR3C) in leukocytes of ALS patients. Here, we show lnc-NR3C promotes p53-mediated cell death in ALS by upregulating USP10 and promoting lnc-NR3C-triggered p53 activation, resulting in cell death. Conversely, lnc-NR3C knockdown inhibited USP10-triggered p53 activation, thereby protecting cells against oxidative stress. As a competitive endogenous RNA, lnc-NR3C competitively binds miR-129-5p, regulating the usp10/p53 axis. Elucidating the link between Lnc-NR3C and the USP10/p53 axis in an ALS cell model reveals a role for long non-coding RNAs in activating apoptosis. This provides new therapeutic opportunities in ALS.

Hybrid neural network wind speed prediction based on two-level decomposition and weighted averaging - Qi Bi; Yu-long Bai; Zai-hong Hou; Rui Wang (Earth Science Informatics, 2024)

Three new furanones from endophytic fungus Hypoxylon vinosopulvinatum DYR-1-7 from Cinnamomum cassia with their antifungal activity - Jia Lv; Hong Zhou; Limei Dong; Hao Wang; Li Yang; Haiqian Yu; Peixi Wu; Le Zhou; Quan Yang; Yongqian Liang; Bi Luo (Natural Product Research, 2024)

Nitrogenous fertilizer plays a more important role than cultivars in shaping sorghum-associated microbiomes - Fangfang Li; Anqi Sun; Xiaoyan Jiao; Dan-Ting Yu; Peixin Ren; Bing-Xue Wu; Peng He; Li Bi; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Metagenomics reveals the potential transmission risk of resistomes from urban park environment to human - Xiaochen Wang; Yuan Qian; Yu Wang; Sijie Wang; Jie Bi; Chenwei Shi; Qian Han; Ruijun Wan-Yan; Qiaoling Yu; Huan Li (Journal of Hazardous Materials, 2024)

The tracement of origins of aquatic products by characterization of their gut or gill microbiome via MALDI-TOF MS analysis - Yuean Chu; Mingyue Yu; Yunxing Li; Suoxian Yang; Hongyan Bi (Food Control, 2024)

Thermal-mechanical coupling smooth particle hydrodynamics-phase field method modelling of cracking in rocks - Zhiqiang Zhou; Jing Bi; Yu Zhao; Chaolin Wang; Yongfa Zhang (Computers and Geotechnics, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

Three new isocoumarin analogues from an endolichenic fungus Aspergillus flavus CPCC 400810 - Ren-Zhong Wang; Bing-Jie Su; Yu-Chuan Chen; Tong-Mei Xiao; Bi-Ying Yan; Li-Yan Yu; Shu-Yi Si; De-Ling Wu; Ming-Hua Chen (Natural Product Research, 2024)

Experimental Investigation on the Effects of Microwave Irradiation in Pore Structures of LN2 Freezing Coal for Coalbed Methane Extraction - Yu Zhao; Zairong Yang; Chaolin Wang; Jing Bi (Rock Mechanics and Rock Engineering, 2024)

H3K4 Trimethylation Mediate Hyperhomocysteinemia Induced Neurodegeneration via Suppressing Histone Acetylation by ANP32A - Gao-shang Chai; Juan Gong; Yu-ming Mao; Jia-jun Wu; Shu-guang Bi; Fangzhou Wang; Yu-qi Zhang; Meng-ting Shen; Zhuo-ya Lei; Yun-juan Nie; Haitao Yu (Molecular Neurobiology, 2024)

Selenium Deficiency Can Promote the Expression of VEGF and Inflammatory Factors in Cartilage Differentiation and Mediates Cartilage Injury - Xiang Meng; Xiumei Meng; Zeju He; Ye Yuan; Yong Fan; Li Yin; Yu Tong; Zheping Hong; Senbo Zhu; Qiong Zhang; Qing Bi (Biological Trace Element Research, 2024)

Effect of different concentrations of carbonate on growth performance, intestinal health and hepatic lipid metabolism of Crucian carp - Xin-yu Lei; Xue Cao; Jia Sun; Chengcheng Bi; Xin Wang; Yue-hong Li (Aquaculture, 2024)

Amino acid mutation of succinate dehydrogenase complex induced resistance to benzovindiflupyr in Magnaporthe oryzae - Liyuan Deng; Mengqing Liu; Yang Yu; Yuheng Yang; Anfei Fang; Binnian Tian; Jing Wang; Chaowei Bi (Pesticide Biochemistry and Physiology, 2024)

Sedimentary record of water-sediment regulation and channel shifts in the Yellow River (Huanghe) Delta - Shuqing Qiao; Xuefa Shi; Jianbu Wang; Lin Zhou; Yonggui Yu; Naishuang Bi; Limin Hu; Gang Yang; Zhengquan Yao (Marine Geology, 2024)

Phenyllactic acid affects cell wall thickness by targeting the synthesis of peptidoglycan in Listeria monocytogenes - Xiaobing Jiang; Mengke Zheng; Mingli Bi; Yiping Zhang; Hong Chen; Lili Zhao; Jiansheng Zhao; Tao Yu (Food Bioscience, 2024)

Sponge iron-coupled biochar solution can achieve the synergistic augmentation of carbon sequestration, carbon sink capacity, and denitrification in ecological ditches - Bi–Ni Jiang; Ying–Ying Zhang; Yan Wang; Hai–qin Liu; Qing Zhou; Yi–Jing Yang; Zhi–Yong Zhang; Yu–Li Yang; Wen–jing Guo; Hai–Liang Song (Chemical Engineering Journal, 2024)

Coupling and synergistic relationships between soil aggregate stability and nutrient stoichiometric characteristics under different microtopographies on karst rocky desertification slopes - Mingfeng Bi; Shuaipu Zhang; Qinxue Xu; Senzheng Hou; Mengwei Han; Xinrui Yu (CATENA, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Copper Homeostasis Based on Cuproptosis-Related Signature Optimizes Molecular Subtyping and Treatment of Glioma - Siyu Zhang; Huihan Yu; Suling Sun; Xiaoqing Fan; Wenxu Bi; Shuyang Li; Wei Wang; Zhiyou Fang; Xueran Chen (Molecular Neurobiology, 2024)

Modified Metal–Organic Framework (MOF-818) inspired by natural enzymes for intelligent detection of total antioxidants and bisphenol A in infant beverages - Jie Li; Luwei Wang; Yu Ma; Zhichun Bi; Yongxin Li; Hui Huang (Analytica Chimica Acta, 2024)

Multi-perspective evaluation of city sustainability and configuration analysis based on fsQCA method: a case study of Liaoning Province, China - Ying Zhou; Tianping Bi; Miao Yu; Chengju Gong (Environment, Development and Sustainability, 2024)

Subduction initiation of Paleo-Pacific Ocean and final closure of Paleo-Asian Ocean: constraints from Triassic granitoids in Jiamusi Block, NE China - Wenjing Bai; Yu Dong; Wenchun Ge; Hao Yang; Junhui Bi; Chen Liu; Jielu Yu; Hongying Zhou; Zheng Ji (International Geology Review, 2024)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Experimental investigation on flame morphology and wall-attached flame temperature of jet flame under the coupled effect of nozzle angle and nozzle-wall spacing - Gaoming Lu; Haiyong Cong; Ziqi Yuan; Zhuyu Shao; Lili Ye; Yubo Bi; Mingshu Bi; Binshan Yu (Fuel, 2024)

Recovery strategies and mechanisms of anammox reaction following inhibition by environmental factors: A review - Shaopo Wang; Yu Tian; Yanmeng Bi; Fansheng Meng; Chunsheng Qiu; Jingjie Yu; Lingjie Liu; Yingxin Zhao (Environmental Research, 2024)

Understanding the links between micro/nanoplastics-induced gut microbes dysbiosis and potential diseases in fish: A review - Yu Cao; Liuliu Bi; Qianqian Chen; Yinai Liu; Haiyang Zhao; Libo Jin; Renyi Peng (Environmental Pollution, 2024)

Victoria amazonica-inspired sandwich-structure interfacial solar steam generator - Junjie Pan; Xin Zhang; Chenglong Zhang; Wenfeng Hu; Siyi Bi; Huiqi Shao; Nanliang Chen; Rui Yu; Jinhua Jiang; Guangwei Shao (Chemical Engineering Journal, 2024)

Suppressing lithium dendrite via hybrid interface layers for high performance quasi-solid-state lithium metal batteries - Bi Luo; Qi Wang; Weijie Ji; Guihui Yu; Zaowen Zhao; Ruirui Zhao; Bao Zhang; Xiaowei Wang; Jiafeng Zhang (Chemical Engineering Journal, 2024)

Lightweight, mechanically robust and scalable cellulose-based foam enabled by organic-inorganic network and air drying - Hao Sun; Hui Zhu; Penghui Zhu; Pu Yang; Zhengyang Yu; Dingyuan Zheng; Xia Sun; Andrea Vo; Xiaotao Bi; Min Xu; Feng Jiang (Chemical Engineering Journal, 2024)

Metabolic engineering of Escherichia coli to efficiently produce 3-deacyl-2-acyloxyacyl-4′-monophosphoryl-lipid A - Aizhen Zhao; Zhen Wang; Jing Yu; Fenfang He; Yibing Bi; Xiaoyuan Wang (Systems Microbiology and Biomanufacturing, 2024)

The failure causes analysis of low-pressure heater pipes based on the porous medium model and local model - Jianfeng Wan; Xiangxuan Xu; Wenyan Bi; Jian Hu; Menglin Yu; Yihong Sun; Qiang Zhou; Yikai Hou; Tianen Li; Xuemao Guan (Annals of Nuclear Energy, 2024)

Interactions of oleanane pentacyclic triterpenoids with human organic anion transporting polypeptide 1B1 and 1B3 - Yiqing Tian; Xue Wang; Yajuan Bi; Xuejuan Li; Yang Zhang; Yao Yao; Mingzhe Zhang; Tong Xu; Youheng Zhang; Chunshan Gui; Weihua Zhang; Chunze Zhang; et al. (Toxicology in Vitro, 2024)

Insight into N2O emission and denitrifier communities under different aeration intensities in composting of cattle manure from perspective of multi-factor interaction analysis - Yue Han; Ruixin Bi; Yuanhang Wang; Lei Sun; Xinda Liu; Shuai Shi; Nuo Chang; Liyan Zhao; Jiaxin Bao; Yonghui Xu; Wanying Liu; Jining Zhang; et al. (Science of The Total Environment, 2024)

New insights into resveratrol attenuates hepatotoxicity in emamectin benzoate-exposed grass carp (Ctenopharyngodon idella) via NO system/NF-κB signaling pathway - Yanju Bi; Haidong Wei; Tingting Yu; Xiaojing Li; Shiwen Xu (Pesticide Biochemistry and Physiology, 2024)

Revealing nitrogenous VX metabolites and the whole-molecule VX metabolism in the urine of guinea pigs - Pei-Yu Jiang; Ling Yuan; Dong-Xin Liu; Hui-Lan Yu; Xiao-Jing Bi; Qiao Lv; Yang Yang; Chang-Cai Liu (Journal of Hazardous Materials, 2024)

Positive legacy effects of grass-legume mixture leys on phosphorus uptake and yield of maize weaken over the growing season - Yujuan He; Yixian Bi; Hongqian Yu; Yingjun Zhang; Paul C. Struik; Jingying Jing (Field Crops Research, 2024)

CFD-DEM numerical investigation of the effects of water content and inclination angle on interactions between debris flows and slit dam - Yandong Bi; Yu Huang; Bei Zhang; Jian Pu (Computers and Geotechnics, 2024)

Large-Scale Fabrication of Customized, Tunable, Ultrathin, and Flexible Metamaterial Absorbers Based on Laser-induced Graphene - Chunhui Chen; Ziyang Jiang; Yu Bai; Menglin Zhai; Fengde Jia; Wenqing Hai; Minghao Li; Jinhua Jiang; Huiqi Shao; Guangwei Shao; Nanliang Chen; Siyi Bi (Chemical Engineering Journal, 2024)

Laboratory study on the frost-proof performance of a molecular vibration infrared Nano-thermoprobe (MVINT) embankment in seasonally frozen ground regions - Zhijian Wu; Guoxu Wang; Jun Bi; Wang Cao; Chengxin Chu; Yu Lu; Tian Sun; Bowen Tai (Cold Regions Science and Technology, 2024)

Centrifuge and DEM investigation of dry granular impacts: Effect of granular volume under high-speed impact conditions - Bei Zhang; Wenyang Li; Jian Pu; Yandong Bi; Yu Huang (Landslides, 2024)

ResDeepSurv: A Survival Model for Deep Neural Networks Based on Residual Blocks and Self-attention Mechanism - Yuchen Wang; Xianchun Kong; Xiao Bi; Lizhen Cui; Hong Yu; Hao Wu (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Nanobodies-based colloidal gold immunochromatographic assay for specific detection of parathion - Mingwei Guo; Jiarui Pang; Yu Wang; Chaohui Bi; Zhenlin Xu; Yudong Shen; Jinyi Yang; Hong Wang; Yuanming Sun (Analytica Chimica Acta, 2024)

Alleviating effect of Astragalus polysaccharide on salinity-alkali stress-induced intestinal injury in hybrid crucian carp - Xin-yu Lei; Jia Sun; Cheng-cheng Bi; Xin Wang; Xue Cao; Hui-qing Wang; Yue-hong Li (Aquaculture International, 2024)

How does technological progress affect low carbon economic growth? Evidence from regional heterogeneity in China - Xi Bi; Huihui Li; Renjin Sun; Nan Yu (Environmental Science and Pollution Research, 2024)

Experimental study on the performance of synergistic ventilation system combining shaft with mechanical ventilation in extra-long road tunnels - Bin Zhu; Haiyong Cong; Binshan Yu; Zhuyu Shao; Lili Ye; Yubo Bi; Yiping Zeng (Tunnelling and Underground Space Technology, 2024)

Study on dynamic behavior and crack propagation mechanism of the tanks in one-step BLEVE accident - Weiye Luo; Jingjie Ren; Di Yu; Zilong Deng; Mingshu Bi (Process Safety and Environmental Protection, 2024)

Lily (Lilium spp.) LhERF4 negatively affects anthocyanin biosynthesis by suppressing LhMYBSPLATTER transcription - Yu-wei Cao; Meng Song; Meng-meng Bi; Pan-pan Yang; Guo-ren He; Jing Wang; Yue Yang; Lei-feng Xu; Jun Ming (Plant Science, 2024)

Biomass-derived polycarboxylate–aluminum–zirconium complex tanning system: A sustainable and practical approach for chrome-free eco-leather manufacturing - Yue Yu; Hui Wang; Yunhang Zeng; Jianfei Zhou; Yi Zhang; Bi Shi; Ya-nan Wang (Journal of Cleaner Production, 2024)

A new comprehensive quantitative index for the assessment of essential amino acid quality in beef using Vis-NIR hyperspectral imaging combined with LSTM - Fujia Dong; Yongzhao Bi; Jie Hao; Sijia Liu; Weiguo Yi; Wenjie Yu; Yu Lv; Jiarui Cui; Hui Li; Jinhua Xian; Sichun Chen; Songlei Wang (Food Chemistry, 2024)

Active Physical Exercise Improves Functional Knee Recovery and Quality of Life Without Increasing the Risk of Complication in Patients with Endoprosthetic Knee Replacement for Bone Tumor - Ning Du; XueLin Zhao; SongZi Cui; Meng Xu; WenZhi Bi; Ji-Guo Yu; YaFeng Song (Journal of Science in Sport and Exercise, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

High dietary wheat starch negatively regulated growth performance, glucose and lipid metabolisms, liver and intestinal health of juvenile largemouth bass, Micropterus salmoides - Bi-Yun Zhang; Hong-Ling Yang; Qing-Jie Nie; Yu Zhang; Guo-He Cai; Yun-Zhang Sun (Fish Physiology and Biochemistry, 2024)

Molecular characterization and functional analysis of peroxiredoxin 1 (Prx1) from roughskin sculpin (Trachidermus fasciatus) - Yingying Liu; Haiyan Cong; Caihong Bi; Haidong Zha; Shanshan Yu; Lihua Zhao; Qian Zhu (Fish Physiology and Biochemistry, 2024)

Preconditioning exercise reduces brain damage of ischemic stroke in rats via PI3K–AKT pathway by bioinformatic analysis - Kai Li; Zhen-Kun Gao; Yi-Sha Guo; Xin-Ya Shen; Yu Han; Mei Yuan; Xia Bi (Experimental Brain Research, 2024)

Clay minerals modified nickel boride for electrochemical supercapacitor electrode application - Fan Yang; Xue-Jing Ma; Jing-Lei Yang; Jun-Hu Liu; Bi Chen; Xin-Yu Liu; Kang Yang; Wei-Bin Zhang (Applied Clay Science, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Cu2O/WO3 S-scheme heterojunctions for photocatalytic degradation of levofloxacin based on coordination activation - Qi Chen; Ling Hu; Yingzhang Shi; Cheng Liu; Yidong Hou; Jinhong Bi; Jimmy C. Yu; Ling Wu (Chemosphere, 2024)

Life cycle environmental and economic assessment of Tetra Pak recycling technologies - Huijuan Dong; Feng Yu; Zhujie Bi; Chenyi Zhang; Xiao Liu; Yong Geng; Satoshi Ohnishi; Haifeng Li (Resources, Conservation and Recycling, 2024)

Remotely sensed retrieval of air-sea carbon flux and acidification risk in Chinese Bohai Sea based on a semi-analytical mechanism model with hour-level GOCI image and ERA5 reanalysis data - Xiang Yu; Yan Liu; Jialin Bi; Xiaoyu Cai; Liping Wang; Liangkun Nie; Chao Qiao; Guanghao Li; Chao Zhan; Guoqing Li; Xianbin Liu; Xiaohui Wang (Journal of Cleaner Production, 2024)

Tree-structured parzen estimator optimized-automated machine learning assisted by meta–analysis for predicting biochar–driven N2O mitigation effect in constructed wetlands - Bi-Ni Jiang; Ying-Ying Zhang; Zhi-Yong Zhang; Yu-Li Yang; Hai-Liang Song (Journal of Environmental Management, 2024)

Provenance and sedimentary environment of REY-rich sediments from the Wharton Basin, Indian Ocean - Jia Li; Mu Huang; Miao Yu; Dongjie Bi; Xuefa Shi; Fengdeng Shi; Chengfei Hou; Zhaojun Song; Fangyu Shen; Aimei Zhu; Hui Zhang; Yonghua Wu; et al. (Journal of Asian Earth Sciences, 2024)

Enhancement of ester biosynthesis in blueberry wines through co-fermentation via cell–cell contact between Torulaspora delbrueckii and Saccharomyces cerevisiae - Yu Wang; Yu Fu; Qi Zhang; Yue Zhu; Qin Yang; Chen Bian; Lu-Lu Zhao; Qi Chen; Hai-Jun Bi; Xiao-Hui Yang; Xue-Ling Gao (Food Research International, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Scalable, mechanically-robust, fire-resistance MXene/PEDOT:PSS/PBO film for efficient electromagnetic interference shielding and Joule heating performance - Haorui Duan; Chuanshen Wang; Yuxiang Yi; Xiaowei Mu; Hongliang Ding; Zhuyun Bi; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Steroidal saponins from the roots of Paris verticillata and their anti-proliferative and anti-inflammatory activities - Yan Liu; Yu Bi; Jin-Ting Bai; Si-Yi Wang; Jia-Tong Wu; Yi-Kai Jiang; Peng Jiang; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

Shale reservoir storage of hydrogen: Adsorption and diffusion on shale - Chaolin Wang; Yu Zhao; Rui Wu; Jing Bi; Kunpeng Zhang (Fuel, 2024)

Improving enzyme accessibility in the aqueous enzymatic extraction process by microwave-induced porous cell walls to increase oil body and protein yields - Xin Guo; Bi-cong Wu; Yun Jiang; Yu Zhang; Bo Jiao; Qiang Wang (Food Hydrocolloids, 2024)

Modulating interfacial charges in CTF-based metal-insulator-semiconductor promotes selective CO2 reduction to CH4 - Qiaoshan Chen; Yueling Chen; Mingfei Yu; Bin Xu; Houyi Wu; Liuyi Li; Jinhong Bi (Chemical Engineering Journal, 2024)

Study on deterioration mechanism of granite with a natural single weak surface after freeze-thaw treatment - Yu Zhao; Bing Liu; Chaolin Wang; Jing Bi; Zedong Yang (Cold Regions Science and Technology, 2024)

Permeability Evolution of Coal Seam Roof Sandstone Under Thermal Treatment - Jing Bi; Kun Zheng; Yu Zhao; Chaolin Wang (Rock Mechanics and Rock Engineering, 2024)

Physical vulnerability of reinforced concrete buildings under debris avalanche impact based on GF-discrepancy and DEM-FEM - Jian Pu; Yu Huang; Zhen Guo; Yandong Bi; Chong Xu; Xingyue Li; Zhiyi Chen (Natural Hazards, 2024)

Experience Learned and Perspectives on Using Model-Integrated Evidence in the Regulatory Context for Generic Drug Products—a Meeting Report - Eleftheria Tsakalozou; Lanyan Fang; Youwei Bi; Michiel van den Heuvel; Tausif Ahmed; Yu Chung Tsang; Robert Lionberger; Amin Rostami-Hodjegan; Liang Zhao (The AAPS Journal, 2024)

Evaluation of energy-environmental-economic benefits of CNG taxi policy using multi-task deep-learning-based microscopic models and big trajectory data - Bi Yu Chen; Qi Liu; Weishu Gong; Jia Tao; Hui-Ping Chen; Fu-Rong Shi (Travel Behaviour and Society, 2024)

Effect of exogenous folate addition on the start-up process of single-stage partial nitritation-anammox system - Xingxing Hu; Lingjie Liu; Yanmeng Bi; Fansheng Meng; Lu Li; Chunsheng Qiu; Jingjie Yu; Shaopo Wang (Process Safety and Environmental Protection, 2024)

Can public opinion persuade the government to strengthen the use of environmental regulation policy tools? Evidence from policy texts - Song Chai; Mengxian Wei; Lin Tang; Xintian Bi; Yawen Yu; Jin Yang; Zhu Jie (Journal of Cleaner Production, 2024)

Combined effects of bedding anisotropy and matrix heterogeneity on hydraulic fracturing of shales from Changning and Lushan, South China: An experimental investigation - Yongfa Zhang; Yu Zhao; Anfa Long; Chaolin Wang; Jing Bi (Journal of Asian Earth Sciences, 2024)

Cell wall modifications during storage: Changes in the texture behavior of the canned yellow peach - Jian Lyu; Xiaoyan Yu; Fengzhao Wang; Jin Xie; Jinfeng Bi (Innovative Food Science & Emerging Technologies, 2024)

Experimental study of a novel quasi-active negative stiffness damper system for achieving optimal active control performance - Huan Li; Kaiming Bi; Hong Hao; Yang Yu; Longhe Xu (Engineering Structures, 2024)

Quaternary-ammonium chitosan, a promising packaging material in the food industry - Yu-Long Qiu; Yixi Li; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Carbohydrate Polymers, 2024)

Lineaperpetua gen. nov.: a new diatom genus in the Thalassiosirales supported by morphology and molecular data - Pan Yu; Lin Yang; Qingmin You; John Patrick Kociolek; Kangyu Wang; Yonghong Bi; Quanxi Wang (Journal of Oceanology and Limnology, 2024)

Field resistance to boscalid and molecular mechanisms of strawberry Botrytis cinerea in Chongqing, China - Pengfei Li; Xueru Yin; Yuheng Yang; Yang Yu; Anfei Fang; Binnian Tian; Chaowei Bi (Australasian Plant Pathology, 2024)

The effect of aperiodic components in distinguishing Alzheimer’s disease from frontotemporal dementia - Zhuyong Wang; Anyang Liu; Jianshen Yu; Pengfei Wang; Yuewei Bi; Sha Xue; Jiajun Zhang; Hongbo Guo; Wangming Zhang (GeroScience, 2023)

Amino carboxymethyl chitosan//dialdehyde starch/polyvinyl alcohol double-layer film loaded with ε-polylysine - Xiaoxia Chen; Yixi Li; Yu-Long Qiu; Gong-Liang Zhang; Hongshun Hao; Hong-Man Hou; Jingran Bi (Food Chemistry, 2023)

Ecological implications of plant clonality - Sergio R. Roiloa; Wei Xue; Bi-Cheng Dong; Fei-Hai Yu (Flora, 2023)

Protein modified cellulose nanocrystals on reinforcement and self-driven biodegradation of aliphatic polyester - Siwen Bi; Zhuang Zhang; Zhenzhen Yang; Zitong Shen; Jiahui Cai; Jintao Hu; Haoxiang Jin; Tianhao Qiu; Peng Yu; Bin Tan (Carbohydrate Polymers, 2023)

Study on Fracture Surface Damage and Fluid Flow Characteristics of Hot Dry Rock with Different Failure Modes under Repeated Thermal Shock - Xiaojiang Deng; Yu Zhao; Jing Bi; Chaolin Wang; Tenglong Liu; Mingxuan Shen; Yang Li (Rock Mechanics and Rock Engineering, 2023)

Behavior of traditional concrete dams and three-dimensional printed concrete dams under the debris flow impact - Hani Meree; Shuai-xing Yan; Dong-po Wang; Yu-zhang Bi (Journal of Mountain Science, 2023)

The chromatin remodeling protein BPTF mediates cell cycle, proliferation and apoptosis in porcine ovarian granulosa cells - Dayu Wang; Xinyue Lu; Yuan Jiang; Linqing Pan; Fuquan Zhu; Aochen Yu; Mingyue Zhao; Meng Yang; Jiaying Bi; Xu He; Honglin Liu; Juan Li (Theriogenology, 2023)

ArfA and SarA small GTPases involved in growth, patulin biosynthesis and virulence of Penicillium expansum - Feng Zhang; Xuemei Zhang; Di Gong; Lirong Yu; Dov Prusky; Edward Sionov; Yang Bi; Yuanyuan Zong (Postharvest Biology and Technology, 2023)

Sodium nitroprusside alleviates nanoplastics-induced developmental toxicity by suppressing apoptosis, ferroptosis and inflammation - Qianqian Chen; Yu Cao; Huiqi Li; Huanpeng Liu; Yinai Liu; Liuliu Bi; Haiyang Zhao; Libo Jin; Renyi Peng (Journal of Environmental Management, 2023)

Effect of pre-harvest sanitizer treatments on Listeria survival, sensory quality and bacterial community dynamics on leafy green vegetables grown under commercial conditions - Hongshan Shang; Bi Zheng Tan; Vongai Dakwa; Erin D'Agnese; Roger A. Stanley; Hannah Sassi; Yu-Wen Lai; Rosalind Deaker; John P. Bowman (Food Research International, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Characterization of shear behavior and damage mechanism of periodic thermal loading sandstone based on NMR technique - Jing Bi; Can Du; Yu Zhao; Chaolin Wang; Shuailong Lian; Xiaohui Xiong (Engineering Geology, 2023)

Nanoscale evidence of zircon-coffinite-xenotime solid solution observed by atom probe tomography - Wenhao Zhao; Bi-Wen Wang; Li-Xin Gu; Xu Tang; Yu Liu; Muhammad Awais; Xiao-Chi Liu; Xian-Hua Li; Rong Hu; Qiu-Li Li (Chemical Geology, 2023)

Achieving advanced nitrogen removal and excess sludge treatment via single nitritation/anammox-fermentation combined system - Jianhua Zhang; Guocheng Ma; Xuejun Bi; Xinchao Zhao; Jiawen Li; Yu Zhang; Zhongxiu Gao; Yitong Li; Yuanyuan Miao (Bioresource Technology, 2023)

Age-specific difference in the temporal relationships between updated cardiovascular health construct and arterial stiffness in middle-aged and older adults - Jiaojiao Huang; Xiaoli Xu; Yingxia Zhou; Zhuojun Xin; Qiuyu Cao; Ruixin He; Tianzhichao Hou; Yi Ding; Jieli Lu; Tiange Wang; Zhiyun Zhao; Yu Xu; et al. (GeroScience, 2023)

Preharvest chitooligosaccharide spray alleviates chilling injury in harvested muskmelon fruit by regulating membrane lipid metabolism and activating antioxidant enzyme activity - Zhanhong Han; Baojun Li; Di Gong; Pengdong Xie; Lirong Yu; Yi Wang; Ye Han; Yongcai Li; Dov Prusky; Gianfranco Romanazzi; Yang Bi (Postharvest Biology and Technology, 2023)

Down-regulation of iron/zinc ion transport and toxin synthesis in Microcystis aeruginosa exposed to 5,4′-dihydroxyflavone - Shumiao Yu; Caicai Xu; Tao Tang; Yiyi Zhang; Kokoette Effiong; Jing Hu; Yonghong Bi; Xi Xiao (Journal of Hazardous Materials, 2023)

Efficient pyridine biodegradation by Stenotrophomonas maltophilia J2: Degradation performance, mechanism, and immobilized application for wastewater - Hongyu Niu; Zimeng Nie; Yu Long; Jiayuan Guo; Ju Tan; Junping Bi; Haijun Yang (Journal of Hazardous Materials, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Orientin regulates the proliferation and migration of hepatocellular carcinoma cells - Jia-Yi Tao; Jing Li; Lu Wan; Bi-Zhen Dong; Yong-Jie Yu; Ye-Mao Liu; Mao-Lin Yi; Li-Peng Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Study on the damage characteristics of concrete-rock composite after exposure to high-temperature environments using nuclear magnetic resonance - Jing Bi; Mingxuan Shen; Yu Zhao; Chaolin Wang; Xiaojiang Deng; Kun Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Organic Carbon Deposition on the Inner Shelf of the East China Sea Constrained by Sea Level and Climatic Changes Since the Last Deglaciation - Mingyu Zhang; Xiting Liu; Fangjian Xu; Anchun Li; Yu Gu; Xin Chang; Guangchao Zhuang; Kaidi Zhang; Naishuang Bi; Houjie Wang (Journal of Ocean University of China, 2023)

Multi-factor coupling analysis and identification of tanks BLEVE - Weiye Luo; Mingshu Bi; Yue Zhang; Di Yu; Zilong Deng; Jingjie Ren (Process Safety and Environmental Protection, 2023)

The component of the Chamaecyparis obtusa essential oil and insecticidal activity against Tribolium castaneum (Herbst) - Lirui Zhang; Yu Zhang; Yanping He; Huang Dai; Zaixi Shu; Wei Zhang; Jie Bi (Pesticide Biochemistry and Physiology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Dilative and compressive Coriolis effect on granular impact behavior based on centrifuge modeling and DEM simulation - Bei Zhang; Wenyang Li; Jian Pu; Yandong Bi; Yu Huang (Engineering Geology, 2023)

A New Close-Form Solution for Elastoplastic Seepage-Induced Stresses to Circular Tunnel with Considering Intermediate Principal Stress - Yu Zhao; Tao Wei; Chaolin Wang; Jing Bi (Rock Mechanics and Rock Engineering, 2023)

Comparative transcriptome analysis of grafting to improve chilling tolerance of cucumber - Xin Fu; Chun-Yu Lv; Yan-Yan Zhang; Xi-Zhen Ai; Huan-Gai Bi (Protoplasma, 2023)

Mongolia Contributed More than 42% of the Dust Concentrations in Northern China in March and April 2023 - Siyu Chen; Dan Zhao; Jianping Huang; Jiaqi He; Yu Chen; Junyan Chen; Hongru Bi; Gaotong Lou; Shikang Du; Yue Zhang; Fan Yang (Advances in Atmospheric Sciences, 2023)

Polysaccharide decolorization: Methods, principles of action, structural and functional characterization, and limitations of current research - Li Tao; Jingwei Zhang; Wenfei Lan; Lei Yu; Yunfeng Bi; Shixin Song; Boyu Xiong; Heyu Wang (Trends in Food Science & Technology, 2023)

Food aflatoxin exposure assessment in Sichuan Province, China - Bi Zhao; Yi Xu; Yang Song; Yu Zhang; Li Lin (Mycotoxin Research, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

Quantifying seasonal ground deformation in Taiyuan basin, China, by Sentinel-1 InSAR time series analysis - Wei Tang; Xiangjun Zhao; Gang Bi; Mingjie Chen; Siyu Cheng; Mingsheng Liao; Wenjun Yu (Journal of Hydrology, 2023)

Seasonal associations between air pollutants and influenza in 10 cities of southern China - Rui Zhang; Yonghong Li; Peng Bi; Siyuan Wu; Zhibin Peng; Yujie Meng; Yu Wang; Songwang Wang; Yushu Huang; Juan Liang; Jing Wu (International Journal of Hygiene and Environmental Health, 2023)

Contribution of theanine to the temperature-induced changes in aroma profile of Wuyi rock tea - Jing Wang; Haijun Bi; Mengru Li; Hui Wang; Manman Xue; Jieyao Yu; Chi-Tang Ho; Liang Zhang; Qinglin Zhuo; Jiadao Jiang; Xiaochun Wan; Xiaoting Zhai (Food Research International, 2023)

Full-spectrum broad-spectrum degradation of antibiotics by BiVO4@BiOCl crystal plane S-type and Z-type heterojunctions - Qian Yang; Guoqiang Tan; Lixiong Yin; Wenlong Liu; Bixin Zhang; Shuaijun Feng; Yu Bi; Ying Liu; Tian Liu; Zeqiong Wang; Huijun Ren; Ao Xia (Chemical Engineering Journal, 2023)

Research on the blocking effect of baffle-net structure on rock avalanches: consider the influence of particle splashing - Yu-Zhang Bi; Dong-Po Wang; Shuai-Xing Yan; Qin-Ze Li; Si-Ming He (Bulletin of Engineering Geology and the Environment, 2023)

Study on the stability and disaster mechanism of layered soil slopes under heavy rain - Yang Li; Kaixi Xue; Yu Zhao; Chaolin Wang; Jing Bi; Tianyuan Wang; Shenfu Wang; Bo Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Chemoreceptors from the commensal gut Roseburia rectibacter bind to mucin and trigger chemotaxis - Hong‐He Chen; Yu‐Xin Wang; De‐Feng Li; Chang Liu; Shuang‐Yu Bi; Cheng‐Ying Jiang; Shuang‐Jiang Liu (Environmental Microbiology, 2023)
Chemotaxis is crucial for bacterial adherence and colonization of the host gastrointestinal tract. Previous studies have demonstrated that chemotaxis affects the virulence of causative pathogens and the infection in the host. However, the chemotactic abilities of non‐pathogenic and commensal gut bacteria have rarely been explored. We observed that Roseburia rectibacter NSJ‐69 exhibited flagella‐dependent motility and chemotaxis to a variety of molecules, including mucin and propionate. A genome‐wide analysis revealed that NSJ‐69 has 28 putative chemoreceptors, 15 of which have periplasmic ligand‐binding domains (LBDs). These LBD‐coding genes were chemically synthesized and expressed heterologously in Escherichia coli . Intensive screening of ligands revealed four chemoreceptors bound to mucin and two bound to propionate. When expressed in Comamonas testosteroni or E. coli , these chemoreceptors elicited chemotaxis toward mucin and propionate. Hybrid chemoreceptors were constructed, and results showed that the chemotactic responses to mucin and propionate were dependent on the LBDs of R. rectibacter chemoreceptors. Our study identified and characterized R. rectibacter chemoreceptors. These results will facilitate further investigations on the involvement of microbial chemotaxis in host colonization.

A new hybrid PM$$_{2.5}$$ volatility forecasting model based on EMD and machine learning algorithms - Ping Wang; Xu Bi; Guisheng Zhang; Mengjiao Yu (Environmental Science and Pollution Research, 2023)

The impacts of spatio-temporal variation of natural and agricultural influences on the environmental water quality in a fluvial-lacustrine watershed in China - Yu Feng; Bing-Hui Zheng; Hai-Feng Jia; Bing-Bing Song; Yang Liu; Jun-Ping Bi (Environmental Science and Pollution Research, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Discard the dross and select the essence: Purified orange peel with coupled alkali-acid hydrolysis as potential Cd(II)-capturing adsorbent - Haoyue Tang; Yu Zhang; You Wu; Wenyu Wu; Shiying Bi; Junjie Wu; Shitong Yang (Journal of Environmental Chemical Engineering, 2023)

The male sterility of bread wheat line XN291S was resulted from the deletion of a large segment at the end of 6BS - Minghu Zhang; Jiazheng Yu; Qijun Xie; Shaozhe Wen; Jinghui Li; Chan Bi; Chaojie Xie; Zhongfu Ni; Rongqi Liang; Mingshan You (Euphytica, 2023)

The novel polyfluoroalkyl benzenesulfonate OBS exposure induces cell cycle arrest and senescence of rat pituitary cell GH3 via the p53/p21/RB pathway - Miao Zhang; Xiaowen Bi; Shuai Liu; Yu Liu; Qiyu Wang (Toxicology, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Numerical simulation the fracture of rock in the framework of plastic-bond-based SPH and its applications - Yu Zhao; Zhiqiang Zhou; Jing Bi; Chaolin Wang; Zhijun Wu (Computers and Geotechnics, 2023)

Finely-tuned heteroleptic phosphorescent Ir(III) complexes for CIEy < 0.2-based pure blue organic light-emitting diodes with external quantum efficiencies > 30% - Jianan Xue; Shuonan Chen; Jie Liang; Hai Bi; Yu Liu; Yue Wang (Chemical Engineering Journal, 2023)

Understanding the impact of pectin on browning of polyphenol oxidation system in thermal and storage processing - Jiaxing Hu; Jinfeng Bi; Xuan Li; Xinye Wu; Wenyue Wang; Qingting Yu (Carbohydrate Polymers, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Analysis of the Microscopic Evolution of Rock Damage Based on Real-Time Nuclear Magnetic Resonance - Jing Bi; Lin Ning; Yu Zhao; Zhijun Wu; Chaolin Wang (Rock Mechanics and Rock Engineering, 2023)

Soil pH change induced by smelting activities affects secondary carbonate production and long-term Cd activity in subsoils - Junwei Wen; Chen Wu; Xiangyang Bi; Sili Zhang; Hao Ouyang; Jiaxin Ye; Toshihiko Ohnuki; Qianqian Yu (Applied Geochemistry, 2023)

An ultra-compact acoustofluidic device based on the narrow-path travelling surface acoustic wave (np-TSAW) for label-free isolation of living circulating tumor cells - Wenping Geng; Yukai Liu; Nanxin Yu; Xiaojun Qiao; Miaomiao Ji; Yaokai Niu; Liya Niu; Wenxiao Fu; Huiyi Zhang; Kaixi Bi; Xiujian Chou (Analytica Chimica Acta, 2023)

Identification of potential necroinflammation-associated necroptosis-related biomarkers for delayed graft function and renal allograft failure: a machine learning-based exploration in the framework of predictive, preventive, and personalized medicine - Qing Bi; Ji-Yue Wu; Xue-Meng Qiu; Yu-Qing Li; Yu-Yao Yan; Ze-Jia Sun; Wei Wang (EPMA Journal, 2023)

Chemical constituents and biological activities of Artemisia argyi H.Lév. & vaniot - Yun-hong Zhang; Zhu-tao Shao; Guang-ming Bi; Yi-wei Sun; Yu-meng Wang; Da-li Meng (Natural Product Research, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Dynamic community detection considering daily rhythms of human mobility - Yuhui Zhao; Bi Yu Chen; Fei Gao; Xinyan Zhu (Travel Behaviour and Society, 2023)

Studies on the interaction of five triazole fungicides with human renal transporters in cells - Jing Nie; Jiabei Zhou; Yi Shen; Ruimiao Lin; Haihong Hu; Kui Zeng; Huichang Bi; Min Huang; Lushan Yu; Su Zeng; Jing Miao (Toxicology in Vitro, 2023)

Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range - Yu Tian; Fenwu Liu; Bo Sun; Zhenye Tong; Peng Fu; Jingzhi Zhang; Wenlong Bi; Shaozu Xu; Guangpeng Pei (Journal of Environmental Chemical Engineering, 2023)

A review of anammox metabolic response to environmental factors: Characteristics and mechanisms - Xiaoying Chen; Lingjie Liu; Yanmeng Bi; Fansheng Meng; Dong Wang; Chunsheng Qiu; Jingjie Yu; Shaopo Wang (Environmental Research, 2023)

Cyclodextrin-functionalized magnetic alginate microspheres for synchronous removal of lead and bisphenol a from contaminated soil - Jianhua Qu; Zhuoran Li; Zhihuan Wu; Fuxuan Bi; Shuqi Wei; Min Dong; Qi Hu; Yifan Wang; Hui Yu; Ying Zhang (Chemical Engineering Journal, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Strain Evolution and Fatigue Damage Characteristics Analysis of Sandstones During Multi-Level Triaxial Cyclic Loading and Unloading Under Varying Stress Limits - Shuang Dang; Jing Bi; Yu Zhao; Chaolin Wang; Jiashen Li; Hao Hu (Rock Mechanics and Rock Engineering, 2023)

Identification of wormholes in soybean leaves based on multi-feature structure and attention mechanism - Wenbo Fang; Fachun Guan; Helong Yu; Chunguang Bi; Yonggang Guo; Yanru cui; Libin Su; Zhengchao Zhang; Jiao Xie (Journal of Plant Diseases and Protection, 2023)

Small GTPases RasA and RasB regulate development, patulin production, and virulence of Penicillium expansum - Yuanyuan Zong; Xuemei Zhang; Di Gong; Feng Zhang; Lirong Yu; Yang Bi; Edward Sionov; Dov Prusky (Postharvest Biology and Technology, 2023)

Deep learning for fluid velocity field estimation: A review - Changdong Yu; Xiaojun Bi; Yiwei Fan (Ocean Engineering, 2023)

Purification performance from bypass ecological treatment systems treating WWTPs effluents and improvement of water quality in receiving rivers: A case study in southern China - Xiaoxu Zheng; Shengjun Xu; Yeliang Bi; Gong Cheng; Shuanglong Ma; Hao Zhang; Cancan Jiang; Cong Wang; Ping Lyu; Yu Qin; Xuliang Zhuang (Journal of Environmental Management, 2023)

Risk assessment of methylmercury and species identification in shark meats ingested by Taiwan children - Bi-Yu Liu; I-Win Chen; Po-Wei Chen; Tai-Yuan Chen; Deng-Fwu Hwang (Food Control, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Facilitating ionic conductivity and interfacial stability via oxygen vacancies-enriched TiO2 microrods for composite polymer electrolytes - Bi Luo; Weigang Wang; Qi Wang; Weijie Ji; Guihui Yu; Zihang Liu; Zaowen Zhao; Xiaowei Wang; Shubin Wang; Jiafeng Zhang (Chemical Engineering Journal, 2023)

P2Y1R and P2Y2R: potential molecular triggers in muscle regeneration - Min-Jia Wang; Bi-Ru Yang; Xin-Yu Jing; Yao-Zheng Wang; Lu Kang; Kai Ren; Liang Kang (Purinergic Signalling, 2023)
Muscle regeneration is indispensable for skeletal muscle health and daily life when injury, muscular disease, and aging occur. Among the muscle regeneration, muscle stem cells’ (MuSCs) activation, proliferation, and differentiation play a key role in muscle regeneration. Purines bind to its specific receptors during muscle development, which transmit environmental stimuli and play a crucial role of modulator of muscle regeneration. Evidences proved P2R expression during development and regeneration of skeletal muscle, both in human and mouse. In contrast to P2XR, which have been extensively investigated in skeletal muscles, the knowledge of P2YR in this tissue is less comprehensive. This review summarized muscle regeneration via P2Y1R and P2Y2R and speculated that P2Y1R and P2Y2R might be potential molecular triggers for MuSCs’ activation and proliferation via the p-ERK1/2 and PLC pathways, explored their cascade effects on skeletal muscle, and proposed P2Y1/2 receptors as potential pharmacological targets in muscle regeneration, to advance the purinergic signaling within muscle and provide promising strategies for alleviating muscular disease.

Pre exposure to enriched environment alleviates brain injury after ischemia-reperfusion by inhibiting p38MAPK/STAT1 pathway - Xin-Ya Shen; Yu Han; Zhen-Kun Gao; Ping-Ping Han; Xia Bi (Molecular Biology Reports, 2023)
Background Stroke is one of the major diseases that endangers human health. It is widely reported that enriched environment (EE) can improve the neurological function in different brain injury models. Recently, relevant researches have indicated that MAPK pathway is closely related to the inflammatory response in nervous system related diseases. However, whether pre exposure to EE (EE pretreatment) has a preventive effect, and its mechanism are not clear. Therefore, this study aimed to determine the possible benefits and related mechanisms of EE in preventing brain injury after acute ischemia-reperfusion. Methods Adult Sprague Dawley rats were kept in enriched or standardized environments for 21 days. Then the middle cerebral artery of rats was occluded for one hour and 30 min, and then reperfusion was performed. Then their neurological deficit score was evaluated. Cerebral edema, along with ELISA and protein quantities of p38MAPK, JNK, ERK, IL-1β, TNF-α, and co-localization of Iba1 were assessed. Changes in neuroinflammation and apoptosis were also detected in the penumbra cortex. Results Our research showed that EE pretreatment significantly alleviated acute cerebral ischemia-reperfusion injury in rats. Including the reduction of brain edema and apoptosis, and the improvement of neurological scores. In addition, the protein level of p38MAPK was significantly down regulated in EE pretreatment group, and the downstream protein STAT1 had the same trend. In addition, immunofluorescence results showed that Iba1 in EE pretreatment group decreased, the ELISA results showed that the classical proinflammatory cytokines increased significantly, while anti-inflammatory cytokines in EE pretreatment group increased, and the same results were obtained by Western blot analysis. Conclusion On the whole, our research demonstrated that EE pretreatment can have a protective effect on the organism by inhibiting the p38 MAPK/STAT1 pathway. Thus, EE can be one of the most promising means of disease prevention. Secondly, p38MAPK/STAT1 pathway may be a latent target for the prevention of acute ischemic stroke.

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Anaerobic co-digestion of three commercial bio-plastic bags with food waste: Effects on methane production and microbial community structure - Cheng Yu; Bi Dongsu; Zhang Tao; Jiang Xintong; Chen Ming; Wang Siqi; Shen Zheng; Zhang Yalei (Science of The Total Environment, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

DEM investigation of the interaction between rapid dry granular flow and dual-slit structures - Yu Huang; Yandong Bi; Bei Zhang (Engineering Geology, 2023)

Cs0.33WO3/(t-m)-BiVO4 double Z-type heterojunction photothermal synergistic enhanced full-spectrum degradation of antibiotics - Qian Yang; Guoqiang Tan; Bixin Zhang; Shuaijun Feng; Yu Bi; Zeqiong Wang; Ao Xia; Huijun Ren; Wenlong Liu (Chemical Engineering Journal, 2023)

Effect of biochars with different particle sizes on fates of antibiotics and antibiotic resistance genes during composting of swine manure - Zhenye Tong; Fenwu Liu; Bo Sun; Yu Tian; Jingzhi Zhang; Jiaze Duan; Wenlong Bi; Junmei Qin; Shaozu Xu (Bioresource Technology, 2023)

Effects of Operating and Media Conditions on the Change of Reclaimed Water Quality in Soil Aquifer Treatment (SAT) System: Experimental and Simulation Study - Heng Gao; Hang Tan; Lecheng Zhu; Yu Ren; Erping Bi (Water, Air, & Soil Pollution, 2023)

Energy Evolution Characteristics of Sandstones During Confining Pressure Cyclic Unloading Conditions - Yu Zhao; Shuang Dang; Jing Bi; Chaolin Wang; Fei Gan; Jiashen Li (Rock Mechanics and Rock Engineering, 2023)

Cerium Oxide Nanoparticles Promote Osteoplastic Precursor Differentiation by Activating the Wnt Pathway - Junchao Luo; Senbo Zhu; Yu Tong; Yin Zhang; Yong Li; Li Cao; Mingxiang Kong; Min Luo; Qing Bi; Qiong Zhang (Biological Trace Element Research, 2023)
Osteoplastic precursors are critical for fracture repair and bone homeostasis maintenance. Cerium oxide nanoparticles (CeO 2 NPs) can promote the osteogenic differentiation of mesenchymal stem cells and secrete vascular endothelial growth factors. However, little is known about its role in precursor osteoblasts; therefore, we further investigated the effect and mechanism of CeO 2 NPs in precursor osteoblasts. Cell counting kit-8 analysis was utilized to detect the toxicity of CeO 2 NPs on MC3T3-E1 mouse osteogenic precursor cells. Then, alizarin red S staining was employed to assess the degree of extracellular matrix mineralization, and quantitative real-time polymerase chain reaction analysis was performed to measure the levels of osteogenesis-related genes. To identify differentially expressed genes, mRNA-sequencing was performed. Subsequently, GO and KEGG analyses were deployed to identify the major downstream pathways, whereas Western blot was used for verification. CeO 2 NPs significantly enhanced the ability of MC3T3-E1 precursor osteoblasts to enhance matrix mineralization and increased the expression of osteogenic genes such as runt-related transcription factor 2, collagen Iα1, and osteocalcin. Pathway analysis revealed that CeO 2 NPs enhanced the nuclear translocation of β-catenin and activated the Wnt pathway by promoting family with sequence similarity 53 member B/simplet expression, while Western blot analysis indicated the same results. After using a Wnt pathway inhibitor (KYA1797K), the simulative effect of CeO 2 NPs was abolished. This study revealed that CeO 2 NPs promoted MC3T3-E1 precursor osteoblast differentiation by activating the Wnt pathway.

Experimental study on the shear mechanical behaviour of rock-like materials containing one embedded flaw under unloading normal stress conditions - Yu Zhao; Mingyang Teng; Jing Bi; Chaolin Wang (European Journal of Environmental and Civil Engineering, 2023)

The accumulation of organic contaminants in hair with different biological characteristics - Bin Tang; Jing Zheng; Shi-Mao Xiong; Feng-Shan Cai; Min Li; Yan Ma; Bo Gao; Dong-Wei Du; Yun-Jiang Yu; Bi-Xian Mai (Chemosphere, 2023)

Acute polyethylene microplastic (PE-MPs) exposure activates the intestinal mucosal immune network pathway in adult zebrafish (Danio rerio) - Yin Yuan; Marisol S. Sepúlveda; Baoliang Bi; Yadong Huang; Lingfu Kong; Hui Yan; Yu Gao (Chemosphere, 2023)

Impacts of springtime biomass burning in Southeast Asia on atmospheric carbonaceous components over the Beibu Gulf in China: Insights from aircraft observations - Xiaoyang Yang; Dongsheng Ji; Jiawei Li; Jun He; Chongshui Gong; Xiaojuan Xu; Zhe Wang; Yu Liu; Fang Bi; Zhongzhi Zhang; Yunbo Chen (Science of The Total Environment, 2023)

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

The effect of three pectin fractions variation on the browning of different dried apple products - Qingting Yu; Xuan Li; Jiaxing Hu; Wenyue Wang; Jinfeng Bi (Food Hydrocolloids, 2023)

Fetal exposure to organic contaminants revealed by infant hair: A preliminary study in south China - Feng-Shan Cai; Bin Tang; Jing Zheng; Xiao Yan; Wei-Keng Luo; Mian He; Xiao-Jun Luo; Ming-Zhong Ren; Yun-Jiang Yu; Bi-Xian Mai (Environmental Pollution, 2023)

Novel double perovskite Ca2Gd0.5Nb1-W5/6O6:0.5 Eu3+ red phosphors with excellent thermal stability and high color purity for white LEDs - Ying Xiang; Zhiyao Liu; Yu Gao; Lei Feng; Ting Zhou; Mengjiao Liu; Yan Zhao; Xin Lai; Jian Bi; Daojiang Gao (Chemical Engineering Journal, 2023)

Cr(VI) adsorption and reduction by magnetite-humic acid adsorption complexes under mildly acidic conditions: Synergistic/antagonistic mechanism and multi-step reaction model - Jingjie Chang; Jia Zhang; Hui Wang; Yunfei Bai; Yu Liu; Yanze Bi; Huanzhen Zhang; Honghan Chen; Samuel Barnie; Haijiao Xie (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Transmembrane protein 106C accelerates the progression of breast cancer through the activation of PI3K/AKT/mTOR signaling - Jian Shang; Xiu Liu; Yanqing Bi; LiXia Yan; Cuiping Tian; Yu Guan (Molecular & Cellular Toxicology, 2023)

Functional characterization of powdery mildew resistance-related genes HbSGT1a and HbSGT1b in Hevea brasiliensis Muell. Arg. - Meng Wang; Huaxing Xiao; Xiaona Li; Sanlian Wan; Ye Yang; Haiyang Yu; Yu Zhang; Bi Qin (European Journal of Plant Pathology, 2023)

Sedimentary record of climate change in a high latitude fjord—Kongsfjord - Hang Wu; Binbin Deng; Jinlong Wang; Sheng Zeng; Juan Du; Peng Yu; Qianqian Bi; Jinzhou Du (Acta Oceanologica Sinica, 2023)

A Stratified NMR-Based Investigation of Spatial Evolution of Pore Structure in Sandstone After Cyclic Heating and Local Water Cooling - Can Du; Jing Bi; Yu Zhao; Chaolin Wang (Natural Resources Research, 2022)

Monitoring and molecular mechanism of boscalid resistance of Sclerotinia sclerotiorum in Southwest China - Pengfei Li; Furong Peng; Ruixuan Zhang; Yuheng Yang; Yang Yu; Chaowei Bi (Journal of Plant Diseases and Protection, 2022)

Hydrothermal carbonization of alfalfa: role of processing variables on hydrochar properties - Jun Zhou; Mingjie Yu; Jianhua Qu; Modupe Sarah Akindolie; Fuxuan Bi; Yang Liu; Zhao Jiang; Lei Wang; Bo Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Influence of multiple porous structure evolution on physical–mechanical properties and damage mechanism of sandstone heated continuously/periodically with the identical heating time - Yu Zhao; Can Du; Jing Bi; Jiashen Li; Chaolin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Investigation of the mechanical behavior and continuum damage model of sandstone after freezing–thawing cycle action under different immersion conditions - Yu Zhao; Shuailong Lian; Jing Bi; Chaolin Wang; Kun Zheng (Bulletin of Engineering Geology and the Environment, 2022)

Complete genome sequence of a novel chrysovirus infecting Talaromyces neofusisporus - Yinhui Jiang; Xun Tian; Xiang Liu; Bi Yang; Nianxue Wang; Qinrong Wang; Wenfeng Yu; Xiaolan Qi; Jian Peng; Tom Hsiang (Archives of Virology, 2022)

Application of a Neural Network to Store and Compute the Optical Properties of Non-Spherical Particles - Jinhe Yu; Lei Bi; Wei Han; Xiaoye Zhang (Advances in Atmospheric Sciences, 2022)
Radiative transfer simulations and remote sensing studies fundamentally require accurate and efficient computation of the optical properties of non-spherical particles. This paper proposes a deep learning (DL) scheme in conjunction with an optical property database to achieve this goal. Deep neural network (DNN) architectures were obtained from a dataset of the optical properties of super-spheroids with extensive shape parameters, size parameters, and refractive indices. The dataset was computed through the invariant imbedding T -matrix method. Four separate DNN architectures were created to compute the extinction efficiency factor, single-scattering albedo, asymmetry factor, and phase matrix. The criterion for designing these neural networks was the achievement of the highest prediction accuracy with minimal DNN parameters. The numerical results demonstrate that the determination coefficients are greater than 0.999 between the prediction values from the neural networks and the truth values from the database, which indicates that the DNN can reproduce the optical properties in the dataset with high accuracy. In addition, the DNN model can robustly predict the optical properties of particles with high accuracy for shape parameters or refractive indices that are unavailable in the database. Importantly, the ratio of the database size (∼127 GB) to that of the DNN parameters (∼20 MB) is approximately 6810, implying that the DNN model can be treated as a highly compressed database that can be used as an alternative to the original database for real-time computing of the optical properties of non-spherical particles in radiative transfer and atmospheric models.

Comparative metabolomics reveal the participation of soybean unique rhizosphere metabolites in susceptibility and resistance of host soybean to Phytophthora sojae - Zhuoqun Zhang; Xiangqi Bi; Xiuming Du; Haixu Liu; Tai An; Yifan Zhao; Han Yu; Yufei Chen; Jingzhi Wen (Plant and Soil, 2022)

Synthesis and biological evaluation of new thiazolyl-urea derivatives as potential dual C-RAF/FLT3 inhibitors - Zhi-Hua Zhang; Bi-Fan Zeng; Zhe-Xue Song; Ying-Yu Yang; Kai-yun Zhang; Xue Du; Lin-lin Zhang; Dong Cai (Medicinal Chemistry Research, 2022)

Vacuum Foam Drying Method Improved the Thermal Stability and Long-Term Shelf Life of a Live Attenuated Newcastle Disease Virus Vaccine - Fang Lyu; Yan-hong Zhao; Yu Lu; Xiao-xin Zuo; Bi-hua Deng; Min-qian Zeng; Jun-ning Wang; Ademola Olaniran; Jibo Hou; Thandeka Khoza (AAPS PharmSciTech, 2022)

Experimental study and particle flow modeling on 3D cracking behavior of rock-like samples with an embedded flaw - Yu Zhao; Daguo Quan; Chaolin Wang; Mingyang Teng; Jing Bi (European Journal of Environmental and Civil Engineering, 2022)

The Rhizosphere Microbial Index Reflects the Optimal Restoration Pattern and the Nutrient Preference of Rhizosphere Microbes of Typical Plants in a Desertified Environment - Boyuan Bi; Chuanyu Wan; Qian Tong; Kun Wang; He Zhang; Yu Wang; Fengpeng Han (Journal of Soil Science and Plant Nutrition, 2022)

Estimation of Active Earth Pressure for Limited Width of Soil Using Nonlinear Failure Criterion - Lu Cong; Xuan-yu Yang; Bi-chang Zhang; Wei Xiong (Geotechnical and Geological Engineering, 2022)

Botrytis cinerea BcSSP2 protein is a late infection phase, cytotoxic effector - Wenjun Zhu; Mengxue Yu; Ran Xu; Kai Bi; Shuang Yu; Chao Xiong; Zhiguo Liu; Amir Sharon; Daohong Jiang; Mingde Wu; Qiongnan Gu; Ling Gong; et al. (Environmental Microbiology, 2022)
Summary Botrytis cinerea is a broad‐host‐range necrotrophic phytopathogen responsible for serious diseases in leading crops. To facilitate infection, B . cinerea secretes a large number of effectors that induce plant cell death. In screening secretome data of B . cinerea during infection stage, we identified a phytotoxic protein (BcSSP2) that can also induce immune resistance in plants. BcSSP2 is a small, cysteine‐rich protein without any known domains. Transient expression of BcSSP2 in leaves caused chlorosis that intensifies with time and eventually leads to death. Point mutations in eight of 10 cysteine residues abolished phytotoxicity, but residual toxic activity remained after heating treatment, suggesting contribution of unknown epitopes to protein phytotoxicity. The expression of bcssp2 was low during the first 36 h after inoculation and increased sharply upon transition to late infection stage. Deletion of bcssp2 did not cause statistically significant changes in lesions size on bean and tobacco leaves. Further analyses indicated that the phytotoxicity of BcSSP2 is negatively regulated by the receptor‐like kinases BAK1 and SOBIR1. Collectively, our findings show that BcSSP2 is an effector protein that toxifies the host cells, but is also recognized by the plant immune system.

Retrieval of Remotely Sensed Sediment Grain Size Evolution Characteristics along the Southwest Coast of Laizhou Bay Based on Support Vector Machine Learning - Xiang Yu; Chao Zhan; Yan Liu; Jialin Bi; Guoqing Li; Buli Cui; Longsheng Wang; Xianbin Liu; Qing Wang (Journal of Marine Science and Engineering, 2022)
Grain size is the basic property of intertidal zone sediment. Grain size acts as an indicator of sedimentary processes and geomorphological evolution under human and nature interactions. The remote sensing technique provides an alternative for sediment grain-size parameter monitoring with the advantages of wide coverage and real-time surveying. This paper attempted to map the distributions of three sediment grain size contents and the mean grain size with multitemporal Landsat images along the southwestern coast of Laizhou Bay, China, from 1989 to 2015. Considering the low correlations between the measured reflectance and grain-size parameters, we used a support vector machine (SVM) to develop a nonlinear calibration model by taking several band indices as input variables. Then, the performance of the back propagation neural network (BPNN) was determined and discussed with that of the SVM. The SVM performed better than the BPNN in calibrating the four grain-size parameters based on a comparison of R2 and the root-mean-square error (RMSE). Moreover, an atmospheric correction algorithm originally proposed for case II water enabled the TM\ETM+ images to be precisely atmospherically corrected in this study. The SVM-mapped spatial-temporal grain-size variation showed a coarsening trend, which agreed with that obtained during in situ measurements in a former study. The changes in Yellow River discharge and precipitation associated with the coarsening trend were further analyzed. The yielded results showed that the coarsening trend and reduction in tidal flat area might be aggravated with overutilization. More reasonable planning would be necessary in this case.

Cross-generation trophic ecology of Dosidicus gigas in the eastern-central Pacific Ocean revealed from isotopic signatures in eye lenses - Guan Yu Hu; Zi Xin Wang; Bi Lin Liu; Meng Yao Huan; Xin Jun Chen (Fisheries Science, 2022)

Experimental investigation of fracture behavior of rock-like materials containing 3D embedded flaws subjected to direct and unloading normal stress shear action - Yu Zhao; Mingyang Teng; Jing Bi; Zheng Li; Pengfei Liu; Chaolin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Complete genome sequence of a novel victorivirus infecting Aspergillus niger - Yinhui Jiang; Xiang Liu; Bi Yang; Xun Tian; Jiayu Liu; Qinrong Wang; Qifang Zhang; Wenfeng Yu; Xiaolan Qi; Tom Hsiang (Archives of Virology, 2022)

Diverse grouping and mating strategies in the Critically Endangered Hainan gibbon (Nomascus hainanus) - Ping Li; Paul A. Garber; Yu Bi; Kun Jin; Xuming Qi; Jiang Zhou (Primates, 2022)
Understanding flexibility in the social structure and mating strategies of the world’s last remaining population (35 individuals) of wild Hainan gibbons ( Nomascus hainanus ) is critical for developing effective management plans to aid in their population recovery. Three of the five remaining Hainan gibbon groups (A, B, and C) currently live in a social unit characterized by two or three adult males, two reproducing adult females, and offspring. A fourth group (D) contains one adult male, two adult females, and offspring, and Group E contains a single adult male–adult female pair with a young infant. In this study, we describe observations of copulations between multiple resident males and one of the two resident females in Group C. Group C is best described as a small multi-male/multi-female group. We found that this breeding female (F2) solicited copulations from two resident adult males (M1 and M2) on the same day, and also mated with each of these two males on different days. Resident males were not observed to interrupt the mating pair. Although factors such as a biased adult sex ratio, severe population disruption, and habitat degradation can help explain variation in group composition and mating strategies in Hainan gibbons, we argue that there exists considerable mating system variability across gibbon species, and that this variability offers important insights into male and female Hainan gibbon group structure and reproductive strategies.

PM2.5-bound phthalates and phthalate substitutes in a megacity of southern China: spatioseasonal variations, source apportionment, and risk assessment - Yu-Qi Huang; Yuan Zeng; Tao Wang; She-Jun Chen; Yu-Feng Guan; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Functional metabolome profiling may improve individual outcomes in colorectal cancer management implementing concepts of predictive, preventive, and personalized medical approach - Yu Yuan; Chenxin Yang; Yingzhi Wang; Mingming Sun; Chenghao Bi; Sitong Sun; Guijiang Sun; Jingpeng Hao; Lingling Li; Changliang Shan; Shuai Zhang; Yubo Li (EPMA Journal, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Transition in tectonic regime from the Paleo-Asian Ocean to Paleo-Pacific Ocean: constraints from the Jurassic adakitic and I-type granites, and calc-alkaline diorites at the northern margin of the North China Craton - Yan Jing; Wen-Chun Ge; Yu Dong; Hao Yang; Zheng Ji; Jun-Hui Bi; Hong-Ying Zhou; De-He Xing (International Geology Review, 2022)

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Optimal array layout of cylindrical baffles to reduce energy of rock avalanche - Yu-zhang Bi; Dong-po Wang; Xian-lei Fu; Yi-xiong Lin; Xin-po Sun; Zhe-yuan Jiang (Journal of Mountain Science, 2022)

Geochronology and Geochemistry of Late Devonian I- and A-Type Granites from the Xing’an Block, NE China: Implications for Slab Break-off during Subduction of the Hegenshan-Heihe Ocean - Zheng Ji; Wenchun Ge; Hao Yang; Yanlong Zhang; Yu Dong; Junhui Bi; Xiwen Liu (Journal of Earth Science, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

The adaptability of Phytophthora sojae to different types of soil determines the distribution of Phytophthora root rot of soybean in Heilongjiang Province of China - Haixu Liu; Han Yu; Zhuoqun Zhang; Xiangqi Bi; Zhiyue Yang; Yufei Chen; Xin Gu; Jingzhi Wen (European Journal of Plant Pathology, 2022)

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Toward an integrated framework for assessing micropollutants in marine mammals: Challenges, progress, and opportunities - Edmond Sanganyado; Ran Bi; Charles Teta; Lucas Buruaem Moreira; Xiaoxuan Yu; Sun Yajing; Tatenda Dalu; Imran Rashid Rajput; Wenhua Liu (Critical Reviews in Environmental Science and Technology, 2021)

The sensitivity of Didymella bryoniae to difenoconazole and boscalid and the synergistic mechanism of fungicide co-formulation - Siyu Liang; Yu Li; Shuntao Liu; Yang Yu; Yuheng Yang; Anfei Fang; Chaowei Bi (European Journal of Plant Pathology, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

The application prospect of metal/metal oxide nanoparticles in the treatment of osteoarthritis - Junchao Luo; Yin Zhang; Senbo Zhu; Yu Tong; Lichen Ji; Wei Zhang; Qiong Zhang; Qing Bi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
The current understanding of osteoarthritis is developing from a mechanical disease caused by cartilage wear to a complex biological response involving inflammation, oxidative stress and other aspects. Nanoparticles are widely used in drug delivery due to its good stability in vivo and cell uptake efficiency. In addition to the above advantages, metal/metal oxide NPs, such as cerium oxide and manganese dioxide, can also simulate the activity of antioxidant enzymes and catalyze the degradation of superoxide anions and hydrogen peroxide. Degrading of metal/metal oxide nanoparticles releases metal ions, which may slow down the progression of osteoarthritis by inhibiting inflammation, promoting cartilage repair and inhibiting cartilage ossification. In present review, we focused on recent research works concerning osteoarthritis treating with metal/metal oxide nanoparticles, and introduced some potential nanoparticles that may have therapeutic effects.

Therapeutic Potential of Cytokines in Demyelinating Lesions After Stroke - Yi-Sha Guo; Mei Yuan; Yu Han; Xin-Ya Shen; Zhen-Kun Gao; Xia Bi (Journal of Molecular Neuroscience, 2021)

LncRNA PTTG3P induced aberrant glycosylated IgA1 production and B cell growth in IgA nephropathy - Min Bi; Jie Shi; Yu Zhao; ChunMei Li (Environmental Science and Pollution Research, 2021)

Effect of Unloading Rate on the Mechanical Behavior and Fracture Characteristics of Sandstones Under Complex Triaxial Stress Conditions - Yu Zhao; Jing Bi; Chaolin Wang; Pengfei Liu (Rock Mechanics and Rock Engineering, 2021)

The Preventive Effects of Lactobacillus casei on Acute Lung Injury Induced by Lipopolysaccharide - Lihui Zhao; Ying Mao; Haiming Yu; He Liu; Chao Wang; Jianwei Liu; Yutong Han; Yang Bi; Donghai Zhang (Indian Journal of Microbiology, 2021)

Experimental investigation of triaxial compression and permeability of gritstone in geothermal environment - Yu Zhao; Can Du; Jing Bi; Chaolin Wang (Bulletin of Engineering Geology and the Environment, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

The exploration of Parkinson’s disease: a multi-modal data analysis of resting functional magnetic resonance imaging and gene data - Xia-an Bi; Hao Wu; Yiming Xie; Lixia Zhang; Xun Luo; Yu Fu (Brain Imaging and Behavior, 2021)

Numerical Prediction of Erosion Based on the Solid-Liquid Two-Phase Flow in a Double-Suction Centrifugal Pump - Xijie Song; Rao Yao; Yubin Shen; Huili Bi; Yu Zhang; Lipu Du; Zhengwei Wang (Journal of Marine Science and Engineering, 2021)
Due to the high sediment content in the Yellow River, the pump units in the pumping stations along the line are often eroded by sediment, causing the reduction of pump efficiency and structural damage. The purpose of this paper is to study the influence of particle diameter on the particle track, erosion distribution and erosion rate in a double-suction centrifugal pump in a pumping station of the Yellow River with a Lagrangian particle-tracking approach and a Tabakoff erosion model. The results show that the surface erosion of the impeller on both sides in the double-suction centrifugal pump has an asymmetric distribution, and the erosion rate on both sides is different. The particle diameter affects the moving trajectory of particles and has a significant effect on the erosion morphology and position in the impeller. With the increase of particle diameter, the velocity of the particles moving towards the pressure side of the blade inlet increases, resulting in punctate impact erosion. When the particle diameter decreases, sliding abrasion gradually forms on the pressure side of the blade outlet. The change rule of the solid particle volume fraction on the impeller wall is consistent with that of erosion distribution on the impeller wall. The larger the solid volume fraction is, the higher the wall erosion rate is.

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Exosomes in bladder cancer: novel biomarkers and targets - Hao Geng; Qingchen Zhou; Wenhao Guo; Ling Lu; Liangkuan Bi; Yi Wang; Jie Min; Dexin Yu; Zhaofeng Liang (Journal of Zhejiang University-SCIENCE B, 2021)

Simulation of Underground Freshwater Exploitation and Analysis of Environmental Impact in Hangzhou Bay New Area, China - Zhiqiang Zhou; Chaolin Wang; Jing Bi; Yu Zhao; Wei Xiang (Natural Resources Research, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Growth influence of juvenile golden trout (Oncorhynchus mykiss) in different osmotic conditions: implications for tissue histology, biochemical indicators, and genes transcription involved in GH/IGF system - Baoliang Bi; Yu Gao; Dan Jia; Lingfu Kong; Yanhua Su; Hua Rong; Xiangwei Wu; Xiaowen Wang; Zhuoyong Hu; Qing Hu (Fish Physiology and Biochemistry, 2021)

The changes of brain functional networks in young adult smokers based on independent component analysis - XianFu Wang; Ting Xue; Fang Dong; Yangding Li; Dongdong Xie; Chang Liu; Ming Zhang; Yanzhi Bi; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2021)

Mass spectrometry-based proteomic analysis of potential infectious bursal disease virus VP3-interacting proteins in chicken embryo fibroblasts cells - Sun-Ting Ma; Yong-Shan Wang; Xiao-Li Wang; Xing-Xia Xia; Zhen-Wei Bi; Jing-Yu Wang; Yu-Mei Zhu; Wei Ouyang; Jing Qian (Virus Genes, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Chromosomal mapping of 5S and 18S-5.8S-25S rRNA genes in Saccharina japonica (Phaeophyceae) as visualized by dual-color fluorescence in situ hybridization - Yu Liu; Pengfei Liu; Yanhui Bi; Zhigang Zhou (Journal of Oceanology and Limnology, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Spatiotemporal characteristics of sea ice transport in the Baffin Bay and its association with atmospheric variability - Weifu Sun; Haibo Bi; Min Fu; Xi Liang; Yunhe Wang; Yu Liang; Jue Huang; Haijun Huang; Liwen Yan; Qinglong Yu; Shuang Liang (Acta Oceanologica Sinica, 2021)

Middle–late permian I-type granitoids from the Diaobingshan region in the northern margin of the North China Craton: insight into southward subduction of the Paleo–Asian Ocean - Yan Jing; Zheng Ji; Wen-Chun Ge; Yu Dong; Hao Yang; Jun-Hui Bi (International Geology Review, 2021)

Molecular cloning and transcriptional regulation of two γ-carbonic anhydrase genes in the green macroalga Ulva prolifera - Yu Wang; Feng Liu; Manman Liu; Shitao Shi; Yuping Bi; Nansheng Chen (Genetica, 2021)

Vertical electric soundings characteristics of paleochannel in the Yuyao River Valley, Eastern China - Yu Zhao; Youcan Yu; Haiqing Yang; Jing Bi (Bulletin of Engineering Geology and the Environment, 2021)

A novel mycovirus infecting Aspergillus nidulans that is closely related to viruses in a new genus of the family Partitiviridae - Yinhui Jiang; Bi Yang; Jiayu Liu; Qinrong Wang; Qifang Zhang; Wenfeng Yu; Tom Hsiang (Archives of Virology, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Erratum to: Arctic multiyear sea ice variability observed from satellites: a review - Haibo Bi; Yu Liang; Yunhe wang; Xi Liang; Zehua Zhang; Tingqin Du; Qinglong Yu; Jue Huang; Mei Kong; Haijin Huang (Journal of Oceanology and Limnology, 2021)

The Role of Reward System in Dishonest Behavior: A Functional Near-Infrared Spectroscopy Study - Yibiao Liang; Genyue Fu; Runxin Yu; Yue Bi; Xiao Pan Ding (Brain Topography, 2021)

Comparative transcriptome combined with morpho-physiological analyses revealed candidate genes potentially for differential cold tolerance in two contrasting apricot (Prunus armeniaca L.) cultivars - Dan Yu; Xiaojuan Liu; Yifan Cui; Quanxin Bi; Yang Zhao; Dongxing Li; Haiyan Yu; Libing Wang (Trees, 2020)

Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Wu-Shan Dong; Peng-Fei Liu; Yu Liu; Yu Du; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2020)

Alpinia oxyphylla–Schisandra chinensis Herb Pair Alleviates Amyloid-β Induced Cognitive Deficits via PI3K/Akt/Gsk-3β/CREB Pathway - Yu Qi; Huiting Jing; Xinhui Cheng; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (NeuroMolecular Medicine, 2020)

Role of atmospheric factors in forcing Arctic sea ice variability - Yu Liang; Haibo Bi; Yunhe Wang; Zehua Zhang; Haijun Huang (Acta Oceanologica Sinica, 2020)

Comparative Variations of Extractive Nitrogenous Components and Quality in Fresh Muscle and Dried Product of Rabbitfish ( Siganus fuscescens ) in Taiwan - Yu-Ru Huang; Wan-Yi Huang; Hsiao-Chin Jen; Bi-Yu Liu; Ken-Meng Huang; Deng Fwu Hwang (Journal of Aquatic Food Product Technology, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Differential response of Phytophthora sojae zoospores to soybean seed exudates provides evidence of seed exudates participate in host resistance - Zhuoqun Zhang; Haixu Liu; Xiangqi Bi; Han Yu; Ying Xu; Yufei Chen; Zhiyue Yang; Jingzhi Wen (Plant and Soil, 2020)

Arctic multiyear sea ice variability observed from satellites: a review - Haibo Bi; Yu Liang; Yunhe Wang; Xi Liang; Zehua Zhang; Tingqin Du; Qinglong Yu; Jue Huang; Mei Kong; Haijun Huang (Journal of Oceanology and Limnology, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

Drought vulnerability assessment for maize in the semiarid region of northwestern China - Ying Wang; Qiang Zhang; Yu-bi Yao (Theoretical and Applied Climatology, 2020)

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Microneedle Array Patch (MAP) Consisting of Crosslinked Hyaluronic Acid Nanoparticles for Processability and Sustained Release - Dae-Sung Kim; Jun-Tae Choi; Cheong Bi Kim; Yu-Ra Shin; Pil-gu Park; Hyemi Kim; Jae Myun Lee; Jung-Hwan Park (Pharmaceutical Research, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

The application of the ‘Gene-deletor’ technology in banana - Chun-hua Hu; Qiao-song Yang; Xiu-hong Shao; Tao Dong; Fang-cheng Bi; Chun-yu Li; Gui-ming Deng; Yi Li; Gan-jun Yi; Tong-xin Dou (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Banana ( Musa spp.) is an important tropical crop. Banana industry is under biotic and abiotic stresses such as Fusarium wilt, typhoon, cold stress. Genetic engineering offers a powerful strategy to create germplasm of banana with enhanced resistance. The safety of genetically modified organisms has become a bottleneck restricting the popularization and application of genetically modified technology. In this study, a candidate promoter, LEAFY (LFY) for expression and flower initiation in Arabidopsis , was cloned and constructed to ‘Gene-deletor’ vector. Histochemical β-glucuronidase (GUS) staining results showed that the ‘Gene-deletor’ vector driven by LFY promoter could lead to 88.5% excision efficiency from Arabidopsis seeds based on more than 200 T 3 progeny examined per event. GUS staining was found to be partially negative in transgenic bananas, however, polymerase chain reaction could still detect the presence of large fragments of the vector. These results suggest that although LFY promoter could not completely drive the ‘Gene-deletor’ vector to achieve the effect of complete elimination of exogenous gene in bananas, its efficiency of eliminating exogenous gene laid a theoretical foundation for cloning banana fruit-specific promoters, that is, ‘non-transgenic’ GM bananas.

Combination of schisandrin and nootkatone exerts neuroprotective effect in Alzheimer’s disease mice model - Yu Qi; Xinhui Cheng; Huiting Jing; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2019)

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Contribution of dissolved organic matter to chemical oxygen demand in three Chinese lakes and in treated sewage - B. Yang; Y. Du; T. Bi; Y. Yu; X. Pan (International Journal of Environmental Science and Technology, 2019)

Wickerhamomyces kurtzmanii sp. nov. An Ascomycetous Yeast Isolated From Crater Lake Water, Da Hinggan Ling Mountain, China - Yu Zhou; Bi-Si Jia; Pei-Jie Han; Qi-Ming Wang; Ai-Hua Li; Yu-Guang Zhou (Current Microbiology, 2019)

Molecular changes in solitary fibrous tumor progression - Hyung Kyu Park; Dan Bi Yu; Minjung Sung; Ensel Oh; Mingi Kim; Ji-Young Song; Mi-Sook Lee; Kyungsoo Jung; Ka-Won Noh; Sungbin An; Kyoung Song; Do-Hyun Nam; et al. (Journal of Molecular Medicine, 2019)

Comparative transcriptome analysis of four co-occurring Ulva species for understanding the dominance of Ulva prolifera in the Yellow Sea green tides - Yu Wang; Feng Liu; Xingfeng Liu; Shitao Shi; Yuping Bi; Fiona Wanjiku Moejes (Journal of Applied Phycology, 2019)

Spatio-temporal variability of phytoplankton assemblages and its controlling factors in spring and summer in the Subei Shoal of Yellow Sea, China - Yuanzi Huo; Honghua Shi; Jianheng Zhang; Qiao Liu; Yuanliang Duan; Qing He; Kefeng Yu; Hongsheng Bi; Chunlei Fan; Peimin He (Acta Oceanologica Sinica, 2019)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

Experimental Analysis on Dynamic Responses of an Electrical Platform for an Offshore Wind Farm under Earthquake Load - Zhen-Zhou Sun; Chun-Wei Bi; Sheng-Xiao Zhao; Guo-Hai Dong; Hua-Feng Yu (Journal of Marine Science and Engineering, 2019)
Offshore wind power is gradually developing to more open sea. Considering the economy of power transmission, it will be an inevitable choice to adopt the extra-large electrical platform. The offshore electrical platform is easily affected by sudden extreme loads such as earthquake and high current loads. With a large volume of electrical equipment arranged on the deck, the offshore electrical platform is characterized as a top-heavy structure in the offshore wind farm. The dynamic effect of the structure will aggravate the vibration problem of the structure. In this paper, a physical model test was carried out to study the dynamic characteristics of the electrical platform of a 10,000-ton offshore converter station under seismic load. The acceleration response, displacement response and stress response of the offshore electrical platform under the typical direction of seismic action were obtained. The effect of the dry–wet environment, mode of seismic excitation, whipping effect and weak positions of electrical platform structure were analyzed. It was determined that the average damping ratio of the first-order mode of the electrical platform was 5.73% and 8.68% with and without water, respectively. The bidirectional seismic excitation was more dangerous to the structure than unidirectional excitation. The peak acceleration along the height of the platform showed a typical whipping effect.

Spatio-temporal patterns of zooplankton in a main-stem dam affected tributary: a case study in the Xiangxi River of the Three Gorges Reservoir, China - Xinghao Li; Jie Huang; Sabine Filker; Thorsten Stoeck; Yonghong Bi; Yuhe Yu; Weibo Song (Science China Life Sciences, 2019)

12-h abstinence-induced functional connectivity density changes and craving in young smokers: a resting-state study - Shuzhi Zhao; Yangding Li; Min Li; Ruonan Wang; Yanzhi Bi; Yajuan Zhang; Xiaoqi Lu; Dahua Yu; Likun Yang; Kai Yuan (Brain Imaging and Behavior, 2019)

Asperpyrone F, a new dimeric naphtho- γ -pyrone from the edible fungus Pleurotus ostreatus - Xu Cai; Yang Yu; Qian Li; Ben-Ke Chen; Yun Huang; Xian-Wei Zou; Jin-Tian Tang; Bi-Sheng Huang (Natural Product Research, 2019)

Pseudomonas qingdaonensis sp. nov., an aflatoxin-degrading bacterium, isolated from peanut rhizospheric soil - Ming-Qing Wang; Zhen Wang; Li-Na Yu; Chu-Shu Zhang; Jie Bi; Jie Sun (Archives of Microbiology, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Two new noroleanane-type triterpenoid saponins from the stems of Stauntonia chinensis - Tong-Tong Feng; Hui-Zheng Fu; Yi-Sheng Yang; Zhi-Qiang Zhou; Mian Dai; Hong-Yu Bi; Dong Wang (Natural Product Research, 2019)

Pharmacokinetic behaviors of ligustrazine after single- and multiple-dose intravenous Shenxiong glucose injection in rats by high-performance liquid chromatography - Qiong Wang; Huaping Sun; Li Yu; Xianpeng Ma; Baoping Jiang; Changqiong Bi; Zhihua Wang; Qinghong Fan; Yuan Yu; Yueheng Liu; Hong Nie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Observed characteristics of tidal currents and mean flow in the northern Yellow Sea - Congcong Bi; Xianwen Bao; Yang Ding; Cong Zhang; Yu Wang; Biao Shen; Kai Wan (Journal of Oceanology and Limnology, 2019)

Intracerebroventricular injection of resveratrol ameliorated Aβ-induced learning and cognitive decline in mice - Yu Qi; Lei Shang; Zhengzheng Liao; Hang Su; Huiting Jing; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2019)

Numerical investigation of effects of “baffles - deceleration strip” hybrid system on rock avalanches - Yu-zhang Bi; Si-ming He; Yan-jun Du; Jie Shan; Shuai-xing Yan; Dong-po Wang; Xin-po Sun (Journal of Mountain Science, 2019)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Physico-mechanical properties of particleboard made from seaweed adhesive and tapioca starch flour - Kang Chiang Liew; Peter Bi De Ting; Yu Feng Tan (Journal of the Indian Academy of Wood Science, 2018)

Direct and legacy effects of herbivory on growth and physiology of a clonal plant - Bi-Cheng Dong; Mo-Zhu Wang; Rui-Hua Liu; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Biological Invasions, 2018)

Recent satellite-derived sea ice volume flux through the Fram Strait: 2011–2015 - Haibo Bi; Yunhe Wang; Wenfeng Zhang; Zehua Zhang; Yu Liang; Yi Zhang; Wenmin Hu; Min Fu; Haijun Huang (Acta Oceanologica Sinica, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Identification of Strategic Residues at the Interface of Antigen–Antibody Interactions by In Silico Mutagenesis - Lu Xin; Hai Yu; Qiyang Hong; Xingjian Bi; Xiao Zhang; Zhiqing Zhang; Zhibo Kong; Qingbing Zheng; Ying Gu; Qinjian Zhao; Jun Zhang; Shaowei Li; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2018)

Comparative Transcriptome Analysis of Rhizoctonia solani-resistant and -Susceptible Rice Cultivars Reveals the Importance of Pathogen Recognition and Active Immune Responses in Host Resistance - Zhengjie Yuan; Yu Zhang; Guojuan Xu; Dongling Bi; Haiyan Qu; Xiaowei Zou; Xiaoqing Gao; Haihe Yang; Haiyan He; Xuli Wang; Jiandong Bao; Shimin Zuo; et al. (Journal of Plant Biology, 2018)

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

Abnormal brain white matter network in young smokers: a graph theory analysis study - Yajuan Zhang; Min Li; Ruonan Wang; Yanzhi Bi; Yangding Li; Zhang Yi; Jixin Liu; Dahua Yu; Kai Yuan (Brain Imaging and Behavior, 2018)

Molecular characterization of a putative gammapartitivirus in the phytopathogenic fungus Nigrospora oryzae - Jin Xiu Yu; Jun Zi Zhu; Ying Wang; Chao Jun Zhang; Jie Zhong; Hong Jian Zhu; Bi Da Gao; Qian Zhou (Archives of Virology, 2018)

Atmospheric deposition of polycyclic aromatic hydrocarbons (PAHs) in Shanghai: the spatio-temporal variation and source identification - Chen Cheng; Chunjuan Bi; Dongqi Wang; Zhongjie Yu; Zhenlou Chen (Frontiers of Earth Science, 2018)

Synthesis and anticonvulsant activity of some novel 7-(benzylamino) -1H-benzo[b][1,4]diazepine-2,4(3H, 5H)-dione derivatives - Yun-Peng Shao; Rong-Bi Han; Hui-Fan Wu; Feng-Yu Piao (Medicinal Chemistry Research, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

New phenanthrene and 9, 10-dihydrophenanthrene derivatives from the stems of Dendrobium officinale with their cytotoxic activities - Gui-Yun Zhao; Bo-Wen Deng; Chong-Yu Zhang; Yi-Da Cui; Jia-Yi Bi; Guo-Gang Zhang (Journal of Natural Medicines, 2018)

Detection and Sizing of Ti-Containing Particles in Recreational Waters Using Single Particle ICP-MS - Arjun K. Venkatesan; Robert B. Reed; Sungyun Lee; Xiangyu Bi; David Hanigan; Yu Yang; James F. Ranville; Pierre Herckes; Paul Westerhoff (Bulletin of Environmental Contamination and Toxicology, 2018)

Combined effects of soil heterogeneity, herbivory and detritivory on growth of the clonal plant Hydrocotyle vulgaris - Lu Liu; Peter Alpert; Bi-Cheng Dong; Jun-Min Li; Fei-Hai Yu (Plant and Soil, 2017)

Plastid Genome of Dictyopteris divaricata (Dictyotales, Phaeophyceae): Understanding the Evolution of Plastid Genomes in Brown Algae - Feng Liu; Zhe Jin; Yu Wang; Yuping Bi; James T. Melton (Marine Biotechnology, 2017)

Identifying apomixis in matroclinal progeny from an interspecific crossing between Iris domestica and three different colors of Iris dichotoma - Fengyang Yu; Wenji Xu; Yuee Xiao; Gangjun Luo; Qingxiang Jia; Yang Zheng; Xiaoying Bi (Euphytica, 2017)

Evaluating Nonlinear Sorption of Four Substituted Phenols to Agriculture Soils Using Expanded Polyparameter Linear Free Energy Relationship - Chenglong Yu; Erping Bi (Water, Air, & Soil Pollution, 2017)

Overexpression of the transcription factor NF-YC9 confers abscisic acid hypersensitivity in Arabidopsis - Chao Bi; Yu Ma; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2017)

Characteristics of agro-meteorological disasters and their risk in Gansu Province against the background of climate change - Ying Wang; Qiang Zhang; Su-Ping Wang; Jin-Song Wang; Yu-bi Yao (Natural Hazards, 2017)

Antioxidant activity of alcohol aqueous extracts of Crypthecodinium cohnii and Schizochytrium sp. - Jin-hui Yu; Yu Wang; Jie Sun; Fei Bian; Gao Chen; Yan Zhang; Yu-ping Bi; Ying-jie Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Record of Permian–Early Triassic continental arc magmatism in the western margin of the Jiamusi Block, NE China: petrogenesis and implications for Paleo-Pacific subduction - Hao Yang; Wenchun Ge; Yu Dong; Junhui Bi; Zhihui Wang; Zheng Ji; H. Yang; W. C. Ge; Y. Dong; J. H. Bi; Z. H. Wang; Z. Ji (International Journal of Earth Sciences, 2017)

Evaluation of resistance of current wheat cultivars and breeding lines to stripe rust from three Gorges reservoir area - Yuheng Yang; Fajing Chen; Dejun Han; Renwu Ruan; Boqun Li; Yang Yu; Chaowei Bi (Journal of General Plant Pathology, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Anti-hepatocellular carcinoma activity of tormentic acid derived from suspension cells of Eriobotrya japonica (Thunb.) Lindl. - Hui-Hua Li; Ming-Hua Su; De-Heng Yao; Bi-Yu Zeng; Qiang Chang; Wei Wang; Jian Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

The implication of salience network abnormalities in young male adult smokers - Yangding Li; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yanzhi Bi; Sha Shi; Ting Xue; Xiaoqi Lu; Wei Qin; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

Neural correlates of 12-h abstinence-induced craving in young adult smokers: a resting-state study - Yangding Li; Kai Yuan; Yanzhi Bi; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Sha Shi; Xiaoqi Lu; Dahua Yu; Jie Tian (Brain Imaging and Behavior, 2017)

The complete chloroplast genome of Lilium taliense, an endangered species endemic to China - Qian Zhang; Yu Bi; Mingfang Zhang; Xuqing Chen; Fengping Yang; Jing Xue; Yunpeng Du; Xiuhai Zhang (Conservation Genetics Resources, 2017)

Using an unmanned aerial vehicle for topography mapping of the fault zone based on structure from motion photogrammetry - Haiyun Bi; Wenjun Zheng; Zhikun Ren; Jiangyuan Zeng; Jingxing Yu (International Journal of Remote Sensing, 2017)

Arabidopsis ABI5 plays a role in regulating ROS homeostasis by activating CATALASE 1 transcription in seed germination - Chao Bi; Yu Ma; Zhen Wu; Yong-Tao Yu; Shan Liang; Kai Lu; Xiao-Fang Wang (Plant Molecular Biology, 2017)

Cytoplasmic expression of a thermostable invertase from Thermotoga maritima in Lactococcus lactis - Han Bin Pek; Pei Yu Lim; Chengcheng Liu; Dong-Yup Lee; Xuezhi Bi; Fong Tian Wong; Dave Siak-Wei Ow (Biotechnology Letters, 2017)

The OPA1 Gene Mutations Are Frequent in Han Chinese Patients with Suspected Optic Neuropathy - A-Mei Zhang; Rui Bi; Qiu-Xiang Hu; Yu Fan; Qingjiong Zhang; Yong-Gang Yao (Molecular Neurobiology, 2017)

Periodic increments in the jumbo squid (Dosidicus gigas) beak: a potential tool for determining age and investigating regional difference in growth rates - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu; Wei Yu; Jin Tao Wang; Jing Yuan Lin (Hydrobiologia, 2017)

Improved Understanding on the Searching Behavior of NSGA-II Operators Using Run-Time Measure Metrics with Application to Water Distribution System Design Problems - Feifei Zheng; Zhexian Qi; Weiwei Bi; Tuqiao Zhang; Tingchao Yu; Yu Shao (Water Resources Management, 2017)

Impacts of sediment type on the performance and composition of submerged macrophyte communities - Lin Liu; Xiang-Qi Bu; Jun-Yan Wan; Bi-Cheng Dong; Fang-Li Luo; Hong-Li Li; Fei-Hai Yu (Aquatic Ecology, 2017)

Erratum to: The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

The Rho kinase inhibitor, fasudil, ameliorates diabetes-induced cardiac dysfunction by improving calcium clearance and actin remodeling - Dongwu Lai; Jing Gao; Xukun Bi; Hong He; Xiaolu Shi; Shaoxiang Weng; Yu Chen; Ying Yang; Yang Ye; Guosheng Fu (Journal of Molecular Medicine, 2017)

Altered resting state functional connectivity of anterior insula in young smokers - Yanzhi Bi; Kai Yuan; Yanyan Guan; Jiadong Cheng; Yajuan Zhang; Yangding Li; Dahua Yu; Wei Qin; Jie Tian (Brain Imaging and Behavior, 2017)

Timosaponin B-II ameliorates scopolamine-induced cognition deficits by attenuating acetylcholinesterase activity and brain oxidative damage in mice - Xu Zhao; Chunmei Liu; Yu Qi; Lina Fang; Jie Luo; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2016)

The complete chloroplast genome sequence of Lilium fargesii (Lilium, Liliaceae) - Yu Bi; Yunpeng Du; Xuqing Chen; Fengping Yang; Jing Xue; Xiuhai Zhang; Ran Dong (Conservation Genetics Resources, 2016)

The complete chloroplast genome of Lilium cernuum: genome structure and evolution - Yunpeng Du; Yu Bi; Xuqing Chen; Fengping Yang; Jing Xue; Xiuhai Zhang (Conservation Genetics Resources, 2016)

A R2R3-MYB transcription factor gene in common wheat (namely TaMYBsm1) involved in enhancement of drought tolerance in transgenic Arabidopsis - Meng-jun Li; Yu Qiao; Ya-qing Li; Zhan-liang Shi; Nan Zhang; Cai-li Bi; Jin-kao Guo (Journal of Plant Research, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Activation of phenylpropanoid pathway and PR of potato tuber against Fusarium sulphureum by fungal elicitor from Trichothecium roseum - Xiao-yan Yu; Yang Bi; Lu Yan; Xiao Liu; Yi Wang; Ke-ping Shen; Yong-cai Li (World Journal of Microbiology and Biotechnology, 2016)

Abnormal prefrontal cortex resting state functional connectivity and severity of internet gaming disorder - Chenwang Jin; Ting Zhang; Chenxi Cai; Yanzhi Bi; Yangding Li; Dahua Yu; Ming Zhang; Kai Yuan (Brain Imaging and Behavior, 2016)

PLD3 in Alzheimer’s Disease: a Modest Effect as Revealed by Updated Association and Expression Analyses - Deng-Feng Zhang; Yu Fan; Dong Wang; Rui Bi; Chen Zhang; Yiru Fang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Prediction of Type II Toxin-Antitoxin Loci in Klebsiella pneumoniae Genome Sequences - Yi-Qing Wei; De-Xi Bi; Dong-Qing Wei; Hong-Yu Ou (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Intra-regional and inter-regional abnormalities and cognitive control deficits in young adult smokers - Dan Feng; Kai Yuan; Yangding Li; Chenxi Cai; Junsen Yin; Yanzhi Bi; Jiadong Cheng; Yanyan Guan; Sha Shi; Dahua Yu; Chenwang Jin; Xiaoqi Lu; et al. (Brain Imaging and Behavior, 2016)

Inhibition control impairments in adolescent smokers: electrophysiological evidence from a Go/NoGo study - Junsen Yin; Kai Yuan; Dan Feng; Jiadong Cheng; Yangding Li; Chenxi Cai; Yanzhi Bi; Shi Sha; Xiaomin Shen; Ben Zhang; Ting Xue; Wei Qin; et al. (Brain Imaging and Behavior, 2016)

Geo-engineered buffer capacity of two-layered absorbing system under the impact of rock avalanches based on Discrete Element Method - Yu-zhang Bi; Si-ming He; Xin-po Li; Yong Wu; Qiang Xu; Chao-jun Ouyang; Li-Jun Su; Hao Wang (Journal of Mountain Science, 2016)

Petrogenesis of Early Cretaceous volcanic rocks of the Manketouebo Formation in the Wuchagou region, central Great Xing’an Range, NE China, and tectonic implications: geochronological, geochemical, and Hf isotopic evidence - Zheng Ji; Wen-Chun Ge; Qing-Hai Wang; Hao Yang; Guo-Chun Zhao; Jun-Hui Bi; Yu Dong (International Geology Review, 2016)

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Interleukin-22 promotes lung cancer cell proliferation and migration via the IL-22R1/STAT3 and IL-22R1/AKT signaling pathways - Yi Bi; Jingyan Cao; Shi Jin; Liyan Lv; Li Qi; Fang Liu; Jianxiong Geng; Yan Yu (Molecular and Cellular Biochemistry, 2016)

Core brain networks interactions and cognitive control in internet gaming disorder individuals in late adolescence/early adulthood - Kai Yuan; Wei Qin; Dahua Yu; Yanzhi Bi; Lihong Xing; Chenwang Jin; Jie Tian (Brain Structure and Function, 2016)

Overexpression of the MYB transcription factor MYB28 or MYB99 confers hypersensitivity to abscisic acid in arabidopsis - Yong-Tao Yu; Zhen Wu; Kai Lu; Chao Bi; Shan Liang; Xiao-Fang Wang; Da-Peng Zhang (Journal of Plant Biology, 2016)

Striatum morphometry is associated with cognitive control deficits and symptom severity in internet gaming disorder - Chenxi Cai; Kai Yuan; Junsen Yin; Dan Feng; Yanzhi Bi; Yangding Li; Dahua Yu; Chenwang Jin; Wei Qin; Jie Tian (Brain Imaging and Behavior, 2016)

Seasonal variations in biochemical composition during the reproductive cycle of the veined rapa whelk Rapana venosa (Valenciennes, 1846) from the northern coast of China - Jinhong Bi; Qi Li; Hong Yu; Zhixin Zhang; Yan Lian; Renjie Wang; Tingyu Wang (Marine Biology Research, 2016)

Overexpression of the MYB37 transcription factor enhances abscisic acid sensitivity, and improves both drought tolerance and seed productivity in Arabidopsis thaliana - Yong-Tao Yu; Zhen Wu; Kai Lu; Chao Bi; Shan Liang; Xiao-Fang Wang; Da-Peng Zhang (Plant Molecular Biology, 2016)

Hepatitis E virus infection activates signal regulator protein α to down-regulate type I interferon - Fen Huang; Chenchen Yang; Wenhai Yu; Yanhong Bi; Feiyan Long; Jue Wang; Yunlong Li; Shenrong Jing (Immunologic Research, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Construction and analysis of the cDNA subtraction library of yeast and mycelial phases of Sporothrix globosa isolated in China: identification of differentially expressed genes - Qing-bi Hu; Yu He; Xun Zhou (Journal of Zhejiang University-SCIENCE B, 2015)

TG-interacting factor mediates arsenic-induced malignant transformation of keratinocytes via c-Src/EGFR/AKT/FOXO3A and redox signalings - Zi-Miao Liu; Hong-Yu Tseng; Bi-Wen Yeh; Wen-Jeng Wu; Huei-Sheng Huang (Archives of Toxicology, 2015)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Clonal integration in homogeneous environments increases performance of Alternanthera philoxeroides - Bi-Cheng Dong; Peter Alpert; Qian Zhang; Fei-Hai Yu (Oecologia, 2015)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

Geographical distribution and risk assessment of persistent organic pollutants in golden threads (Nemipterus virgatus) from the northern South China Sea - Qing Hao; Yu-Xin Sun; Xiang-Rong Xu; Zi-Wei Yao; You-Shao Wang; Zai-Wang Zhang; Xiao-Jun Luo; Bi-Xian Mai (Ecotoxicology, 2015)

Determination of squid age using upper beak rostrum sections: technique improvement and comparison with the statolith - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu (Marine Biology, 2015)

Satellite-Based Investigation and Evaluation of the Observational Environment of Meteorological Stations in Anhui Province, China - Yu-Bin Li; Tao Shi; Yuan-Jian Yang; Bi-Wen Wu; La-Bao Wang; Chun-E Shi; Jian-Xia Guo; Cheng-Li Ji; Hua-Yang Wen (Pure and Applied Geophysics, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Projecting Future Transmission of Malaria Under Climate Change Scenarios: Challenges and Research Needs - Weiwei Yu; Kerrie Mengersen; Pat Dale; Xiaofang Ye; Yuming Guo; Lyle Turner; Xiaoyu Wang; Yan Bi; William J. H. McBride; John S. Mackenzie; Shilu Tong (Critical Reviews in Environmental Science and Technology, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Clinical assessment and polysomnographic study of sleep apnea in a Chinese population of snorers - Chuan Shao; Jing-bo Jiang; Hong-cheng Wu; Shi-bo Wu; Bi-yun Yu; Yao-dong Tang (Journal of Zhejiang University-SCIENCE B, 2015)

Enhanced adsorptive removal of selected pharmaceutical antibiotics from aqueous solution by activated graphene - Fei Yu; Jie Ma; Dongsu Bi (Environmental Science and Pollution Research, 2015)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

Microarray analysis of long non-coding RNAs in COPD lung tissue - Hui Bi; Ji Zhou; Dandan Wu; Wei Gao; Lingling Li; Like Yu; Feng Liu; Mao Huang; Ian M. Adcock; Peter J. Barnes; Xin Yao (Inflammation Research, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Improved synthesis of phosphatidylserine using bio-based solvents, limonene and p-cymene - Yan-Hong Bi; Zhang-Qun Duan; Wen-Ying Du; Zhao-Yu Wang (Biotechnology Letters, 2015)

Dysfunction of hippocampal interneurons in epilepsy - Yu-Qiang Liu; Fang Yu; Wan-Hong Liu; Xiao-Hua He; Bi-Wen Peng (Neuroscience Bulletin, 2014)

Molecular cloning and expression of a novel MYB transcription factor gene in rubber tree - Bi Qin; Yu Zhang; Meng Wang (Molecular Biology Reports, 2014)

Impact of Intracranial Artery Disease and Prior Cerebral Infarction on Central Nervous System Complications After Off-Pump Coronary Artery Bypass Grafting - Q. Bi; J.-Yu Li; X.-Q. Li; Q. Li; D. Luo; Q.-B. Qiao (Neurophysiology, 2014)

Phylogeography of Chinese house mice ( Mus musculus musculus/castaneus ): distribution, routes of colonization and geographic regions of hybridization - Meidong Jing; Hon‐Tsen Yu; Xiaoxin Bi; Yung‐Chih Lai; Wei Jiang; Ling Huang (Molecular Ecology, 2014)
House mice ( Mus musculus ) are human commensals and have served as a primary model in biomedical, ecological and evolutionary research. Although there is detailed knowledge of the biogeography of house mice in Europe, little is known of the history of house mice in China, despite the fact that China encompasses an enormous portion of their range. In the present study, 535 house mice caught from 29 localities in China were studied by sequencing the mitochondrial D‐loop and genotyping 10 nuclear microsatellite markers distributed on 10 chromosomes. Phylogenetic analyses revealed two evolutionary lineages corresponding to Mus musculus castaneus and Mus musculus musculus in the south and north, respectively, with the Yangtze River approximately representing the boundary. More detailed analyses combining published sequence data from mice sampled in neighbouring countries revealed the migration routes of the two subspecies into China: M . m . castaneus appeared to have migrated through a southern route (Yunnan and Guangxi), whereas M . m . musculus entered China from Kazakhstan through the north‐west border (Xinjiang). Bayesian analysis of mitochondrial sequences indicated rapid population expansions in both subspecies, approximately 4650–9300 and 7150–14 300 years ago for M . m . castaneus and M . m . musculus , respectively. Interestingly, the migration routes of Chinese house mice coincide with the colonization routes of modern humans into China, and the expansion times of house mice are consistent with the development of agriculture in southern and northern China, respectively. Finally, our study confirmed the existence of a hybrid zone between M . m . castaneus and M . m . musculus in China. Further study of this hybrid zone will provide a useful counterpart to the well‐studied hybrid zone between M . m . musculus and Mus musculus domesticus in central Europe.

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Predicting DNA-binding sites of proteins based on sequential and 3D structural information - Bi-Qing Li; Kai-Yan Feng; Juan Ding; Yu-Dong Cai (Molecular Genetics and Genomics, 2014)

Synthesis and anticonvulsant evaluation of some new 1,3,4,5-tetrahydro-6-alkoxy-2H-1-benzazepin-2-one derivatives - Rong-Bi Han; Yun-Peng Shao; Hui-Fan Wu; Duo Zhang; Feng-Yu Piao (Medicinal Chemistry Research, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Upregulated Expression of NF-YC Contributes to Neuronal Apoptosis via Proapoptotic Protein Bim in Rats’ Brain Hippocampus Following Middle Cerebral Artery Occlusion (MCAO) - Yunfeng Wang; Chunhua Wan; Shanshan Yu; Lixiang Yang; Bing Li; Ting Lu; Yongfeng Bi; Junkang Jiang; Gang Cui (Journal of Molecular Neuroscience, 2014)

Characterization of α-type carbonic anhydrase (CA) gene and subcellular localization of α-CA in the gametophytes of Saccharina japonica - R.-X. Ye; Z. Yu; W.-W. Shi; H.-J. Gao; Y.-H. Bi; Z.-G. Zhou (Journal of Applied Phycology, 2014)

Overexpression of PtSOS2 Enhances Salt Tolerance in Transgenic Poplars - Jie Zhou; Jingjing Wang; Yufang Bi; Like Wang; Luozhong Tang; Xiang Yu; Misato Ohtani; Taku Demura; Qiang Zhuge (Plant Molecular Biology Reporter, 2014)

Taxonomy and phylogeny of Ceriporia (Polyporales, Basidiomycota) with an emphasis of Chinese collections - Bi-Si Jia; Li-Wei Zhou; Bao-Kai Cui; Bernard Rivoire; Yu-Cheng Dai (Mycological Progress, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Estimation of tropical cyclone parameters and wind fields from SAR images - Xuan Zhou; XiaoFeng Yang; ZiWei Li; Yang Yu; HaiBo Bi; Sheng Ma; XiaoFeng Li (Science China Earth Sciences, 2013)

Impacts of Urbanization and Station-relocation on Surface Air Temperature Series in Anhui Province, China - Yuan-Jian Yang; Bi-Wen Wu; Chun-e Shi; Jia-Hua Zhang; Yu-Bin Li; Wei-An Tang; Hua-Yang Wen; Hong-Qun Zhang; Tao Shi (Pure and Applied Geophysics, 2013)

Phosphorus loads from different urban storm runoff sources in southern China: a case study in Wenzhou City - Dong Zhou; Chun-Juan Bi; Zhen-Lou Chen; Zhong-Jie Yu; Jun Wang; Jing-Chao Han (Environmental Science and Pollution Research, 2013)

Electron transfer capacity of soil dissolved organic matter and its potential impact on soil respiration - Ran Bi; Qin Lu; Weimin Yu; Yong Yuan; Shungui Zhou (Journal of Soils and Sediments, 2013)

Identification of MV-generated ROS responsive EST clones in floral buds of Litchi chinensis Sonn. - Wei-Wei Liu; Hye-Ji Kim; Hou-Bin Chen; Xing-Yu Lu; Bi-Yan Zhou (Plant Cell Reports, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Retrieving the antarctic sea-ice concentration based on AMSR-E 89 GHz data - Qinglong Yu; Hui Wang; Liying Wan; Haibo Bi (Acta Oceanologica Sinica, 2013)

Protein structure and gene expression study of phytochrome B in maize - Zhuang Li; Yu-Bi Huang (Journal of Plant Biochemistry and Biotechnology, 2013)

Multi-angle Indicators System of Non-point Pollution Source Assessment in Rural Areas: A Case Study Near Taihu Lake - Lei Huang; Jie Ban; Yu Ting Han; Jie Yang; Jun Bi (Environmental Management, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Heavy metals in urban ambient PM10 and soil background in eight cities around China - Qiong Wang; Xiao-Hui Bi; Jian-Hui Wu; Yu-Fen Zhang; Yin-Chang Feng (Environmental Monitoring and Assessment, 2013)

The interaction of banana MADS-box protein MuMADS1 and ubiquitin-activating enzyme E-MuUBA in post-harvest banana fruit - Ju-Hua Liu; Jing Zhang; Cai-Hong Jia; Jian-Bin Zhang; Jia-Shui Wang; Zi-Xian Yang; Bi-Yu Xu; Zhi-Qiang Jin (Plant Cell Reports, 2013)

Spatial–temporal dynamics of NDVI and Chl-a concentration from 1998 to 2009 in the East coastal zone of China: integrating terrestrial and oceanic components - Xiyong Hou; Mingjie Li; Meng Gao; Liangju Yu; Xiaoli Bi (Environmental Monitoring and Assessment, 2013)

Methodology for antibody preparation and detection of southern rice black-streaked dwarf virus - Zhuo Chen; Chengjun Yin; Jiaju Liu; Mengjiao Zeng; Zhenchao Wang; Dandan Yu; Liang Bi; Linhong Jin; Song Yang; Baoan Song (Archives of Virology, 2012)

Isolation, Characterization, and Expression Analysis of the MuBTB Gene in Banana - Cai-Hong Jia; Zhi-Qiang Jin; Ju-Hua Liu; Jian-Bin Zhang; Jia-Shui Wang; Bi-Yu Xu (Plant Molecular Biology Reporter, 2012)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

Synthesis and anticonvulsant activity of 8-alkoxy-5,6-dihydro-4H-benzo[f][1,2,4]triazolo[4,3-a]azepine derivatives - Wen-Bin Zhang; Rong-Bi Han; Wei Zhang; Ri-Shan Jiang; Feng-Yu Piao (Medicinal Chemistry Research, 2012)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Relating hydrograph components to rainfall and streamflow: a case study from northern Taiwan - Yu-Ji Li; Shin-jen Cheng; Tsang-Long Pao; Yi-jie Bi (Hydrological Sciences Journal, 2012)

IL-1β: an important cytokine associated with febrile seizures? - Hong-Mei Yu; Wan-Hong Liu; Xiao-Hua He; Bi-Wen Peng (Neuroscience Bulletin, 2012)

Effects of fragmentation on the survival and growth of the invasive, clonal plant Alternanthera philoxeroides - Bi-Cheng Dong; Peter Alpert; Wei Guo; Fei-Hai Yu (Biological Invasions, 2012)

Purification, Characterization, and Expression Analysis of a Putative Lectin in Peanut (Arachis hypogaea L.) - Sun Jie; Zhang Chu-shu; Yu Li-na; Bi Jie; Liu Shao-fang; Zhu Feng; Yang Qing-li (Plant Molecular Biology Reporter, 2012)

Serotonin accumulation in transgenic rice by over-expressing tryptophan decarboxlyase results in a dark brown phenotype and stunted growth - Parawee Kanjanaphachoat; Bi-Yin Wei; Shuen-Fang Lo; I-Wen Wang; Chang-Sheng Wang; Su-May Yu; Ming-Liang Yen; Sheng-Hsien Chiu; Chien-Chen Lai; Liang-Jwu Chen (Plant Molecular Biology, 2012)

Angelica sinensis (Oliv.) Diels in China: distribution, cultivation, utilization and variation - Hong Yi Zhang; Wen Gang Bi; Yi Yu; Wen Bo Liao (Genetic Resources and Crop Evolution, 2012)

Allelic variation and distribution of HMW glutenin subunit 1Ay in Triticum species - Xi-Gui Hu; Bi-Hua Wu; Zhe-Guang Bi; Deng-Cai Liu; Lian-Quan Zhang; Ze-Hong Yan; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Identification and expression analysis of four 14-3-3 genes during fruit ripening in banana (Musa acuminata L. AAA group, cv. Brazilian) - Mei-Ying Li; Bi-Yu Xu; Ju-Hua Liu; Xiao-Liang Yang; Jian-Bin Zhang; Cai-Hong Jia; Li-Cheng Ren; Zhi-Qiang Jin (Plant Cell Reports, 2012)

Regioselectivity-reversal in acylation of 6-azauridine catalyzed by Burkholderia cepacia lipase - Zhao-Yu Wang; Yan-Hong Bi; Min-Hua Zong (Biotechnology Letters, 2012)

Curcumin promotes cholesterol efflux from adipocytes related to PPARgamma–LXRalpha–ABCA1 passway - Shao-zhuang Dong; Shui-ping Zhao; Zhi-hong Wu; Jun Yang; Xiang-zhu Xie; Bi-lian Yu; Sai Nie (Molecular and Cellular Biochemistry, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Effect of Homobaric Pure Oxygen on Sensory Gating in the Human Brain - Qiu Hong Yu; Jie Yang; Kim Yuan He; Lian Bi Xue; Andrew CN Chen (Brain Topography, 2011)

Phytoplankton variation and its relationship with the environment in Xiangxi Bay in spring after damming of the Three-Gorges, China - Guangjie Zhou; Xuemin Zhao; Yonghong Bi; Yubin Liang; Jianlin Hu; Min Yang; Yu Mei; Kongxian Zhu; Lin Zhang; Zhengyu Hu (Environmental Monitoring and Assessment, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

Inhibition of Hydrogen Sulfide Generation Contributes to 1-Methy-4-Phenylpyridinium Ion-Induced Neurotoxicity - Xiao-Qing Tang; Li-Li Fan; Yu-Juan Li; Xin-Tian Shen; Yuan-Yuan Zhuan; Jian-Qin He; Jin-Hua Xu; Bi Hu; Yuan-Jian Li (Neurotoxicity Research, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

How internode length, position and presence of leaves affect survival and growth of Alternanthera philoxeroides after fragmentation? - Bi-Cheng Dong; Guo-Lei Yu; Wei Guo; Ming-Xiang Zhang; Ming Dong; Fei-Hai Yu (Evolutionary Ecology, 2010)

Polybrominated Diphenyl Ethers (PBDEs), Polychlorinated Biphenyles (PCBs), Hydroxylated and Methoxylated-PBDEs, and Methylsulfonyl-PCBs in Bird Serum from South China - Juan Liu; Xiao-Jun Luo; Le-Huan Yu; Ming-Jing He; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2010)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

Floral development in Impatiens chishuiensis (Balsaminaceae): formation of two well-developed anterolateral sepals and four carpels - S. X. Yu; X.-R. Zhou; G.-F. Xu; L. Meng; H.-Y. Bi (Plant Systematics and Evolution, 2010)

Expression and characterization of two domains of Pinellia ternata agglutinin (PTA), a plant agglutinin from Pinellia ternata with antifungal activity - Li-Jun Ling; Yan-Zhuo Yang; Yu-Rong Bi (World Journal of Microbiology and Biotechnology, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Assessing heavy-metal contamination and sources by GIS-based approach and multivariate analysis of urban–rural topsoils in Wuhan, central China - Min Gong; Li Wu; Xiang-yang Bi; Li-min Ren; Lei Wang; Zhen-dong Ma; Zheng-yu Bao; Zhong-gen Li (Environmental Geochemistry and Health, 2010)

Assessment on environmental quality of heavy metals in agricultural soils of Chongming Island, Shanghai City - Chao Sun; Chunjuan Bi; Zhenlou Chen; Dongqi Wang; Cui Zhang; Yuedi Sun; Zhongjie Yu; Dong Zhou (Journal of Geographical Sciences, 2010)

Comparative proteomic analysis of apomictic monosomic addition line of Beta corolliflora and Beta vulgaris L. in sugar beet - Hong Zhu; Ying-Dong Bi; Li-Jie Yu; De-Dong Guo; Bai-Chen Wang (Molecular Biology Reports, 2009)

Isolation and characterization of 12 microsatellite loci from cutlassfish (Trichiurus haumela) - Jin-Zhen Bi; Chang-Wei Shao; Gui-Dong Miao; Hong-Yu Ma; Song-Lin Chen (Conservation Genetics, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Constitutive and Induced Activities of Defense-Related Enzymes in Aphid-Resistant and Aphid-Susceptible Cultivars of Wheat - Ying Han; Yu Wang; Jian-Long Bi; Xiao-Qin Yang; Yong Huang; Xin Zhao; Yuan Hu; Qing-Nian Cai (Journal of Chemical Ecology, 2009)

Deletion analysis of SMN1 and NAIP genes in southern Chinese children with spinal muscular atrophy - Yu-hua Liang; Xiao-ling Chen; Zhong-sheng Yu; Chun-yue Chen; Sheng Bi; Lian-gen Mao; Bo-lin Zhou; Xian-ning Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

STS markers for powdery mildew resistance gene Pm6 in wheat - Jianhui Ji; Bi Qin; Haiyan Wang; Aizhong Cao; Suling Wang; Peidu Chen; Lifang Zhuang; Yu Du; Dajun Liu; Xiue Wang (Euphytica, 2008)

Akt/PKB interacts with the histone H3 methyltransferase SETDB1 and coordinates to silence gene expression - Haidong Gao; Zhigang Yu; Dongsong Bi; Liyu Jiang; Yazhou Cui; Jingzhong Sun; Rong Ma (Molecular and Cellular Biochemistry, 2007)

Differentially expressed cDNAs at the early stage of banana ripening identified by suppression subtractive hybridization and cDNA microarray - Bi Yu Xu; Wei Su; Ju Hua Liu; Jia Bao Wang; Zhi Qiang Jin (Planta, 2007)

EfficientAgrobacterium-mediated transformation of rice by phosphomannose isomerase/mannose selection - Ding Zai-Song; Zhao Ming; Jing Yu-Xiang; Li Liang-Bi; Kuang Ting-Yun (Plant Molecular Biology Reporter, 2006)

Impact of plant breeding on genetic diversity of the Canadian hard red spring wheat germplasm as revealed by EST-derived SSR markers - Yong-Bi Fu; Gregory W. Peterson; Ju-Kyung Yu; Lifeng Gao; Jizeng Jia; Ken W. Richards (Theoretical and Applied Genetics, 2006)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Estimation of Normal Variance Based on Balanced and Unbalanced Ranked Set Samples - Philip L.H. Yu; Kin Lam; Bi Mal K. Sinha (Environmental and Ecological Statistics, 1999)